Developing carrier, developer, process cartridge, image forming apparatus, and image forming method

By placing a resin composition containing specific inorganic particles in the internal voids of the magnetic particles, the problem of uneven image density in the electrostatic charge image development method under high temperature and high humidity environment is solved, and a more uniform image formation is achieved.

CN119472197APending Publication Date: 2025-02-18FUJIFILM BUSINESS INNOVATION CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411070408.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-08-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When using AC voltage development in high temperature and high humidity environments, the internal voids of magnetic particles in the carrier for electrostatic charge image development do not contain inorganic particles, resulting in uneven image density.

Method used

A resin composition including inorganic particles selected from silica, alumina, and calcium carbonate and a resin are arranged in the inner voids of the magnetic particles to suppress unevenness in the image.

Benefits of technology

By placing the resin composition, the dielectric constant of the carrier is reduced, the responsiveness to the AC voltage is improved, and the image density uneven formed in a high temperature and high humidity environment is suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119472197A_ABST
    Figure CN119472197A_ABST
Patent Text Reader

Abstract

The invention discloses a carrier for developing, a developer, a process cartridge, an image forming apparatus, and a method, the carrier for developing an electrostatic charge image having: magnetic particles having internal voids; and a resin composition that is disposed in at least a portion of the internal voids and contains a resin and inorganic particles containing at least one selected from the group consisting of silica, alumina, and calcium carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carrier for developing an electrostatic charge image, an electrostatic charge image developer, a processing box, an image forming device and an image forming method. Background Art

[0002] In Japanese Patent Publication No. 2019-061188, there is disclosed a carrier for electrophotographic development, which is coated with a resin on the surface of a carrier core material, the carrier core material is composed of ferrite particles, has a specific pore volume, and an average internal void area is within a specific range, and the void area is 20 μm 2 The internal void ratio of the above internal voids is 1.8% or less.

[0003] In addition, Japanese Patent Gazette No. 2021-051216 discloses a carrier for electrostatic charge image development, which has a core material and a coating resin layer, wherein the coating resin layer contains nitrogen-containing resin particles and inorganic oxide particles and coats the core material, and the surface exposure rate of the nitrogen-containing resin particles is greater than 0.8% and less than 3.0%.

[0004] In addition, Japanese Patent Application Laid-Open No. 2007-058124 discloses a carrier for electrostatic latent image development, which comprises core particles and a resin coating layer in which conductive fine particles are dispersed, and is characterized in that:

[0005] The average particle size of the carrier is 25 to 60 μm, the average roundness is 0.975 or more, and the BET specific surface area of ​​the core particle is 0.1 to 0.3 m 2 / g, and the internal porosity is less than 10%. Summary of the invention

[0006] An object of the present invention is to provide an electrostatic image developing carrier which can suppress density unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where no inorganic particles are contained in the internal voids of magnetic particles.

[0007] According to a first embodiment of the present invention, there is provided a carrier for developing electrostatic charge images, comprising: magnetic particles having internal voids; and a resin composition, the resin composition being arranged in at least a portion of the internal voids and containing inorganic particles comprising at least one selected from the group consisting of silica, alumina, and calcium carbonate, and a resin.

[0008] According to a second aspect of the present invention, in the electrostatic image developing carrier according to the first aspect, the internal void ratio of the magnetic particles is 2% or more and 10% or less.

[0009] According to a third aspect of the present invention, in the electrostatic image developing carrier according to the first or second aspect, in a cross section of the resin composition, a ratio of a total area of ​​the inorganic particles to a total area of ​​the resin is 0.02 to 0.10.

[0010] According to the fourth embodiment of the present invention, in the electrostatic charge image developing carrier involved in any one of the first to third embodiments, the resin composition does not contain conductive particles; or contains the conductive particles, and in the cross-section of the resin composition, the ratio of the total area of ​​the conductive particles to the total area of ​​the inorganic particles is less than 0.005.

[0011] According to a fifth aspect of the present invention, in the electrostatic image developing carrier according to any one of the first to fourth aspects, the inorganic particles have a number average particle size of 5 nm or more and 90 nm or less.

[0012] According to a sixth aspect of the present invention, in the electrostatic image developing carrier according to any one of the first to fifth aspects, the resin includes a resin having nitrogen atoms.

[0013] According to a seventh aspect of the present invention, in the electrostatic image developing carrier according to the sixth aspect, the resin further includes a resin having no nitrogen atom.

[0014] According to an eighth aspect of the present invention, in the electrostatic image developing carrier according to the first aspect, there is provided a resin coating layer, wherein the resin coating layer coats the magnetic particles and contains a resin and inorganic particles.

[0015] According to the ninth aspect of the present invention, in the electrostatic charge image developing carrier involved in the eighth aspect, when the ratio of the total area of ​​the inorganic particles contained in the resin coating layer to the overall area of ​​the resin coating layer in the cross section of the resin coating layer is set to area ratio A, and the ratio of the total area of ​​the inorganic particles contained in the resin composition to the overall area of ​​the resin composition in the cross section of the resin composition is set to area ratio B, the area ratio A is greater than 10% and less than 50%, and the area ratio A>area ratio B.

[0016] According to a tenth aspect of the present invention, in the electrostatic image developing carrier according to the ninth aspect, the area ratio B is 0.05 times or more and 0.3 times or less of the area ratio A.

[0017] According to an eleventh aspect of the present invention, there is provided an electrostatic image developer comprising: an electrostatic image developing toner; and the electrostatic image developing carrier according to any one of the first to tenth aspects.

[0018] According to the twelfth aspect of the present invention, a processing box is provided, which has a developing device, and the developing device accommodates the electrostatic charge image developer involved in the eleventh aspect. The electrostatic charge image formed on the surface of the image retaining body is developed into a colorant image by the electrostatic charge image developer. The processing box is installed and removed from the image forming device.

[0019] According to the thirteenth scheme of the present invention, there is provided an image forming device, which comprises: an image retaining body; a charging device, which charges the surface of the image retaining body; an electrostatic charge image forming device, which forms an electrostatic charge image on the surface of the image retaining body after charging; a developing device, which accommodates the electrostatic charge image developer involved in the eleventh scheme, and develops the electrostatic charge image formed on the surface of the image retaining body into a colorant image through the electrostatic charge image developer; a transfer device, which transfers the colorant image formed on the surface of the image retaining body to the surface of a recording medium; and a fixing device, which fixes the colorant image transferred to the surface of the recording medium.

[0020] According to the fourteenth aspect of the present invention, there is provided an image forming method, comprising: a charging process for charging the surface of an image retaining body; an electrostatic charge image forming process for forming an electrostatic charge image on the surface of the image retaining body after charging; a developing process for developing the electrostatic charge image formed on the surface of the image retaining body into a colorant image by using the electrostatic charge image developer according to the eleventh aspect; a transfer process for transferring the colorant image formed on the surface of the image retaining body to the surface of a recording medium; and a fixing process for fixing the colorant image transferred to the surface of the recording medium.

[0021] (Effect)

[0022] According to the first aspect, there is provided an electrostatic image developing carrier which suppresses density unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where no inorganic particles are contained in the internal spaces of magnetic particles.

[0023] According to the second aspect, there is provided an electrostatic image developing carrier which suppresses density unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where the internal porosity of magnetic particles is less than 2% or exceeds 10%.

[0024] According to the third embodiment, there is provided a carrier for electrostatic image development, which suppresses the concentration unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where the ratio of the total area of ​​inorganic particles to the total area of ​​resin in a cross section of the resin composition is less than 0.02 or exceeds 0.10.

[0025] According to the fourth embodiment, there is provided a carrier for electrostatic image development, which suppresses the concentration unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where the ratio of the total area of ​​the conductive particles to the total area of ​​the inorganic particles in the cross section of the resin composition exceeds 0.005.

[0026] According to the fifth aspect, there is provided an electrostatic image developing carrier which suppresses density unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where the number average particle size of inorganic particles is less than 5 nm or exceeds 90 nm.

[0027] According to the sixth aspect, there is provided an electrostatic image developing carrier which suppresses density unevenness of an image formed by a development method in which an AC voltage is applied under a high temperature and high humidity environment, compared with a case where the resin does not contain a resin having a nitrogen atom.

[0028] According to the seventh aspect, there is provided an electrostatic image developing carrier which can suppress the poor environment of image density compared with the case where the resin is composed of a resin having nitrogen atoms.

[0029] According to the eighth scheme, there is provided an electrostatic charge image developing carrier which, compared with a case where the resin coating layer or the resin composition arranged in the internal voids does not contain inorganic particles, suppresses the adhesion of the electrostatic charge image developing carrier to the image retaining body when an image with a high image density is continuously formed for a long time under high temperature and high humidity.

[0030] According to the ninth scheme, there is provided an electrostatic charge image developing carrier which, compared with the case where the area ratio A is less than 10% or exceeds 50%, or the area ratio A ≤ the area ratio B, suppresses the adhesion of the electrostatic charge image developing carrier to the image retaining body when an image with high image density is continuously formed for a long time under high temperature and high humidity.

[0031] According to the tenth scheme, there is provided an electrostatic charge image developing carrier which, compared with a case where the area ratio B is less than 0.05 times or exceeds 0.3 times the area ratio A, suppresses the adhesion of the electrostatic charge image developing carrier to the image retaining body when an image with high image density is continuously formed for a long time under high temperature and high humidity.

[0032] According to the eleventh, twelfth, thirteenth, or fourteenth scheme, an electrostatic charge image developer, a processing box, an image forming device, or an image forming method is provided, which suppresses the uneven concentration of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with the case of an electrostatic charge image developing carrier that does not contain inorganic particles in the internal gaps of magnetic particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a schematic diagram for explaining a method for confirming internal voids of magnetic particles;

[0034] Figure 2 is a schematic structural diagram showing an example of an image forming apparatus according to the present embodiment;

[0035] Figure 3 This is a schematic structural diagram showing an example of a process cartridge that is attached to and detached from the image forming apparatus according to the present embodiment. DETAILED DESCRIPTION

[0036] The following describes embodiments of the present invention. These descriptions and examples are intended to illustrate the embodiments and do not limit the scope of the embodiments.

[0037] In the present invention, a numerical range expressed using "to" indicates a range including the numerical values ​​described before and after "to" as the minimum value and the maximum value, respectively.

[0038] In the numerical range of recording in stages in the present invention, the upper limit or lower limit recorded in a numerical range can also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range of recording in the present invention, the upper limit or lower limit of this numerical range can also be replaced by the value shown in the embodiment.

[0039] In the present invention, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.

[0040] In the present invention, when the embodiments are described with reference to the drawings, the structure of the embodiments is not limited to the structure shown in the drawings. In addition, the sizes of the components in each figure are conceptual sizes, and the relative relationship between the sizes of the components is not limited to this.

[0041] In the present invention, each component may also include a plurality of corresponding substances. In the present invention, when referring to the amount of each component in the composition, in the case where there are a plurality of substances equivalent to each component in the composition, unless otherwise specifically stated, the amount of each component refers to the total amount of the plurality of substances present in the composition.

[0042] The present invention may include a plurality of particles corresponding to each component. When a plurality of particles corresponding to each component are present in the composition, the particle size of each component refers to a value for a mixture of the plurality of particles present in the composition unless otherwise specified.

[0043] In the present invention, “(meth)acryl” means at least one of acryl and methacryl, and “(meth)acrylate” means at least one of acrylate and methacrylate.

[0044] In the present invention, “toner for electrostatic image development” is also referred to as “toner”, “carrier for electrostatic image development” is also referred to as “carrier”, and “electrostatic image developer” is also referred to as “developer”.

[0045] [Carrier for electrostatic image development]

[0046] The carrier for electrostatic charge image development of the present embodiment comprises: magnetic particles having internal voids; and a resin composition, which is disposed in at least a portion of the internal voids and contains inorganic particles and resins containing at least one selected from the group consisting of silica, alumina, and calcium carbonate. The carrier of the present embodiment may further have a resin coating layer coating the magnetic particles as required.

[0047] Hereinafter, inorganic particles containing at least one selected from the group consisting of silica, alumina, and calcium carbonate are also referred to as “specific inorganic particles”, and a resin composition containing the specific inorganic particles and a resin is also referred to as a “specific resin composition”.

[0048] In this embodiment, by placing a specific resin composition in the internal voids of the magnetic particles, density unevenness of an image formed by a development method in which an AC voltage is applied under a high temperature and high humidity environment is suppressed. The reason for this is not clear, but is presumed as follows.

[0049] One of the causes of uneven density of images formed by a development method in which an AC voltage is applied is poor responsiveness of the carrier to the AC voltage. In particular, it is believed that the higher the dielectric constant of the carrier as a whole, the slower the response to the AC voltage in a high temperature and high humidity environment, and the more likely it is to cause image unevenness.

[0050] In addition, another reason for the uneven density of an image formed by a development method in which an AC voltage is applied is the generation of cracks and notches in magnetic particles serving as a core material of a carrier. The cracks and notches in the magnetic particles are generated, for example, by the application of a mechanical load by stirring in a developing device. Furthermore, it is believed that the generation of cracks and notches in the magnetic particles causes a change in the chargeability of a portion of the carrier, resulting in regions with different densities in the formed image, causing image unevenness.

[0051] In contrast, in the present embodiment, a specific resin composition containing specific inorganic particles is disposed in the internal voids of the magnetic particles. It is believed that the specific inorganic particles have a low relative dielectric constant, so by being present in the internal voids of the magnetic particles, the dielectric constant of the entire carrier becomes lower, and the responsiveness to the AC voltage is improved. Moreover, it is speculated that due to the improved responsiveness to the AC voltage, even if a solid image is formed under a high temperature and high humidity environment, the voltage change is small, the attachment of the toner is close to uniform, and the concentration unevenness is suppressed.

[0052] In addition, it is believed that because there is resin in the internal voids of the magnetic particles, the mechanical load is relieved by the elasticity of the resin, thereby suppressing cracks and gaps in the magnetic particles. Furthermore, it is speculated that since cracks and gaps in the magnetic particles are suppressed, the generation of image unevenness caused by cracks and gaps in the magnetic particles is suppressed.

[0053] For the above reasons, it is presumed that in the present embodiment, density unevenness of an image formed by a development method in which an AC voltage is applied under a high-temperature and high-humidity environment is suppressed.

[0054] The carrier according to this embodiment is described in detail below.

[0055] <Magnetic particles>

[0056] There is no limitation on the magnetic particles as long as they have internal voids.

[0057] Specific examples of the magnetic particles include particles of magnetic oxides such as ferrite and magnetite. The magnetic particles are preferably particles of magnetic oxides, and more preferably ferrite particles.

[0058] From the viewpoint of suppressing image unevenness, the internal porosity of the magnetic particles is preferably 2% to 10%, more preferably 2% to 8%, and still more preferably 3% to 6%.

[0059] When the internal porosity of the magnetic particles is greater than the above lower limit, the specific inorganic particles are likely to be present in the internal voids of the magnetic particles, and the dielectric constant of the carrier as a whole is likely to be lowered. As a result, it is believed that the responsiveness to the alternating voltage is improved, and the generation of uneven density of images formed by a development method applying an alternating voltage under a high temperature and high humidity environment is suppressed.

[0060] Furthermore, it is considered that when the internal porosity of the magnetic particles is equal to or less than the upper limit, cracks and chips of the magnetic particles due to a mechanical load are less likely to occur, and the occurrence of image unevenness due to such cracks and chips is suppressed.

[0061] As a method for adjusting the internal porosity of the magnetic particles to the above range, for example, when the magnetic particles are ferrite particles, the method of controlling the oxygen concentration and the calcination temperature during calcination can be cited. Specifically, the internal porosity increases by increasing the oxygen concentration or decreasing the calcination temperature.

[0062] Confirmation that the magnetic particles have internal voids and calculation of the internal void ratio of the magnetic particles were performed as follows.

[0063] First, after embedding the carrier with an embedding agent such as epoxy resin to obtain an embedded product, the surface of the embedded product is cut with a diamond knife or the like. The cutting is continued until the position of the cross section of the magnetic particles is fully ensured, and the cross section is photographed as a sample for measurement. The cross section photography can also be performed by a conventionally known method such as a scanning electron microscope (SEM).

[0064] Next, a cross section of one particle of the magnetic particles is analyzed using conventionally known image analysis software (for example, WinRoof (Mitani Shoji Co., Ltd.)). Specifically, Figure 1 As shown, the void existing in the square 220 (i.e., the space where no magnetic particles exist) is confirmed, and the square 220 has two points 218a and 218b on a diameter 214 of the circumscribed circle 212 of the particle on the cross section 210 of the magnetic particle, which are 3 / 4 of the length of the radius from the center 216 of the circumscribed circle 212 as two relative vertices.

[0065] Whether the magnetic particles have internal voids is confirmed by analyzing the cross section of 100 magnetic particles and confirming whether voids exist in the square 220. In the SEM image of the cross section of the magnetic particles, voids appear as black areas.

[0066] When the presence of voids in the square 220 is confirmed in the cross sections of 90 or more magnetic particles, the particles are regarded as magnetic particles having internal voids.

[0067] The internal void ratio (%) of the magnetic particles is calculated by the following formula: wherein SH is the total area of ​​voids present in the squares 220 in 100 magnetic particles, and ST is the total area of ​​the squares 220 in 100 magnetic particles.

[0068] Formula: Internal void ratio (%) = (SH / ST) × 100

[0069] In addition, a diameter 214 of a circumscribed circle 212 of a magnetic particle on a cross section 210 of the magnetic particle is selected as a diameter at an arbitrary position. In addition, the cross section 210 of the magnetic particle to be measured is preferably a cross section cut near the center of the magnetic particle.

[0070] From the viewpoint of obtaining a moderate adhesion between the colorant and the carrier to obtain a sufficient amount of colorant development, and obtaining an appropriate magnetic brush to form an image with excellent fine line reproducibility, the number average particle size of the magnetic particles is preferably greater than 15 μm and less than 100 μm, more preferably greater than 20 μm and less than 80 μm, and further preferably greater than 30 μm and less than 60 μm.

[0071] In addition, the number average particle size of the magnetic particles is obtained by analyzing the cross section of 100 magnetic particles in the same manner as the method for confirming the internal voids in the magnetic particles described above. Specifically, the equivalent circle diameter of the cross section 210 of each particle is obtained, and the value averaged for the 100 particles is set as the number average particle size of the magnetic particles.

[0072] The magnetic force of the magnetic particles is preferably 50emu / g or more in a magnetic field of 3000 oersteds, and more preferably 60emu / g or more. The above-mentioned saturation magnetization is measured using a vibrating sample magnetometer VSMP10-15 (manufactured by Dongying Industry Co., Ltd.). The test sample is loaded into a cell with an inner diameter of 7mm and a height of 5mm and placed on the magnetometer. An external magnetic field is applied and the maximum scan is 3000 oersteds for measurement. Next, the external magnetic field is reduced and a hysteresis curve is made on a recording paper. Based on the curve data, the saturation magnetization, residual magnetization, and holding force are calculated.

[0073] The volume resistance (volume resistivity) of the magnetic particles is preferably 1×10 5 Ω·cm or more and 1×10 9 Ω·cm or less, more preferably 1×10 7 Ω·cm or more and 1×10 9 Ω·cm or less.

[0074] The volume resistivity (Ω·cm) of the magnetic particles is measured as follows. The object to be measured is placed flatly on a 20 cm 2 The 20 cm 2 The layers are sandwiched between electrode plates. In order to eliminate the gaps between the measured objects, a load of 4 kg is applied to the electrode plates arranged on the layers, and then the thickness of the layers (cm) is measured. The upper and lower electrodes of the layers are connected to an electrometer and a high-voltage power supply generator. A high voltage is applied to the two electrodes so that the electric field reaches 103.8 V / cm, and the current value (A) flowing at this time is read. The measurement environment is set to a temperature of 20°C and a relative humidity of 50%. The calculation formula for the volume resistivity (Ω·cm) of the measured object is shown below.

[0075] R=E×20 / (I-I0) / L

[0076] In the above formula, R represents the volume resistance of the object to be measured (Ω·cm), E represents the applied voltage (V), I represents the current value (A), I0 represents the current value (A) at an applied voltage of 0V, and L represents the thickness of the layer (cm). The coefficient 20 represents the area of ​​the electrode plate (cm 2 ).

[0077] <Specific resin composition>

[0078] The specific resin composition is configured in at least a portion of the internal voids of the magnetic particles. The magnetic particles may have at least an internal void configured with the specific resin composition, or may also have an internal void not configured with the specific resin composition. As the internal void not configured with the specific resin composition, there may be cited an internal void only configured with a resin, an internal void only configured with specific inorganic particles, an internal void not configured with both resin and specific inorganic particles, and the like.

[0079] The confirmation that a specific resin composition is arranged in the internal voids of the magnetic particles is carried out by observing and analyzing the cross-section of the magnetic particles in the same manner as the confirmation method of the internal voids in the magnetic particles described above. For example, in the case where the specific inorganic particles are silica, the cross-section of the internal voids of the magnetic particles is elementally analyzed by energy dispersive X-ray fluorescence spectrometry (EDX), and the area where silica is present is confirmed by drawing the area where silicon is present, and the area where resin is present is confirmed by drawing the area where carbon is present. In addition, in the case where the specific inorganic particles are alumina, it is confirmed by drawing the area where aluminum elements are present, and in the case where the specific inorganic particles are calcium carbonate, it is confirmed by drawing the area where calcium elements are present.

[0080] The specific resin composition contains at least specific inorganic particles and a resin, and may further contain other components.

[0081] Confirmation that the specific resin composition is connected to the resin coating layer is also performed by observing the cross section of the carrier in the same manner as confirmation that the specific resin composition is arranged in the internal voids of the magnetic particles.

[0082] (Specific inorganic particles)

[0083] The specific inorganic particles contained in the specific resin composition are at least one selected from the group consisting of silica, alumina, and calcium carbonate. The specific inorganic particles can be composed of only one inorganic particle, or can be composed of two or more inorganic particles. Among them, from the viewpoint of suppressing uneven concentration by lowering the dielectric constant of the entire carrier, the specific inorganic particles preferably include silica.

[0084] The surface of specific inorganic particles can also implement hydrophobic treatment. In the case where specific inorganic particles include silicon dioxide, as a hydrophobic treatment agent, for example, known organosilicon compounds with alkyl groups (such as methyl, ethyl, propyl, butyl, etc.) can be enumerated, and in a specific example, alkoxysilane compounds, siloxane compounds, silazane compounds, etc. can be enumerated. Wherein, the hydrophobic treatment agent is preferably a silazane compound, preferably hexamethyldisilazane. The hydrophobic treatment agent can be used alone or in combination with two or more.

[0085] By performing the hydrophobic treatment, the inorganic particles can be easily dispersed uniformly in the resin composition. Therefore, the dielectric constant of the entire carrier is lowered, and thus concentration variation is suppressed.

[0086] As a method for hydrophobizing specific inorganic particles by using a hydrophobizing agent, for example, there can be mentioned: a method in which a hydrophobizing agent is dissolved in supercritical carbon dioxide using supercritical carbon dioxide, and the hydrophobizing agent is attached to the surface of specific inorganic particles; a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is applied (for example, sprayed or coated) to the surface of specific inorganic particles in the atmosphere, and the hydrophobizing agent is attached to the surface of specific inorganic particles; a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is added to a specific inorganic particle dispersion in the atmosphere and maintained, and then a mixed solution of the specific inorganic particle dispersion and the solution is dried.

[0087] From the viewpoint of suppressing concentration variation, the number average particle size of the specific inorganic particles is preferably 5 nm to 90 nm, more preferably 5 nm to 50 nm, and even more preferably 7 nm to 50 nm.

[0088] It is believed that by having the number average particle size of the specific inorganic particles within the above-mentioned range, compared with the case where the number average particle size of the specific inorganic particles is larger than the above-mentioned range or smaller than the above-mentioned range, it is less likely to produce cracks, gaps, etc. in the magnetic particles caused by mechanical loads, thereby suppressing the occurrence of image unevenness caused by them.

[0089] The number average particle size of the specific inorganic particles is obtained by analyzing the cross section of the magnetic particles in the same manner as the method for confirming the internal voids in the magnetic particles described above. Specifically, the value obtained by calculating the equivalent circle diameter of each particle for 100 specific inorganic particles present in the internal voids of the magnetic particles and averaging the equivalent circle diameter is set as the number average particle size of the specific inorganic particles.

[0090] It is preferred to observe and analyze using a field emission scanning electron microscope (FE-SEM) capable of high-resolution photography. Specific examples of FE-SEM include Hitachi High-Technologies' Regulus series "SU8010", "Regulus8100", "Regulus8220", "Regulus8230", "Regulus8240", "ULT RA55", and JEOL's "JSM-IT800".

[0091] In addition, as the number average particle size of the inorganic particles contained in the specific resin composition and the resin coating layer, the number average particle size of the inorganic particles measured by a laser diffraction / scattering particle size distribution analyzer may be used.

[0092] The amount of the specific inorganic particles contained in the specific resin composition is preferably such that the ratio of the total area of ​​the specific inorganic particles to the total area of ​​the resin in the cross section of the specific resin composition is 0.02 to 0.10.

[0093] Hereinafter, the ratio of the total area SP of the specific inorganic particles in the cross section of the specific resin composition to the total area SR of the resin is also referred to as the area ratio (SP / SR). The area ratio (SP / SR) is preferably 0.02 to 0.10, more preferably 0.03 to 0.08, and further preferably 0.04 to 0.06.

[0094] When the area ratio (SP / SR) is equal to or greater than the lower limit, the dielectric constant of the entire carrier tends to be lowered, which is believed to improve the responsiveness to AC voltage and suppress the occurrence of density unevenness in an image formed by a development method applying AC voltage under a high temperature and high humidity environment.

[0095] Furthermore, it is considered that when the area ratio (SP / SR) is below the upper limit, the mechanical load is relieved by the resin present in the internal voids of the magnetic particles, and cracks and chips of the magnetic particles are less likely to occur, thereby suppressing the occurrence of image unevenness caused by such cracks and chips.

[0096] The area ratio (SP / SR) is obtained by cross-sectional analysis of 100 specific resin compositions contained in the internal voids of the magnetic particles in the same manner as the confirmation method for configuring a specific resin composition in the internal voids of the magnetic particles described above. Specifically, the total area of ​​the region of the specific inorganic particles in the 100 specific resin compositions and the total area of ​​the region of the resin are obtained to calculate the area ratio (SP / SR).

[0097] (resin)

[0098] Examples of the resin contained in the specific resin composition include: styrene-acrylic copolymers; polyolefin resins such as polyethylene and polypropylene; polyvinyl or polyvinylidene resins such as polystyrene, (meth)acrylic resins, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymers; ordinary silicone resins composed of organic siloxane bonds or modified products thereof; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyesters; polyurethanes; polycarbonates; amino resins such as urea formaldehyde resins; epoxy resins, etc.

[0099] Among them, from the viewpoint of reducing the dielectric constant of the carrier by improving the affinity with the inorganic particles and thus suppressing concentration unevenness, the resin contained in the specific resin composition preferably contains a (meth)acrylic resin, more preferably contains 50% by mass or more of the (meth)acrylic resin relative to the total mass of the resin in the specific resin composition, and particularly preferably contains 80% by mass or more of the (meth)acrylic resin relative to the total mass of the resin in the specific resin composition.

[0100] From the viewpoint of reducing the dielectric constant of the carrier by increasing the affinity with the inorganic particles and thus suppressing the uneven concentration, the specific resin composition preferably contains a (meth) acrylic resin having an alicyclic structure. The (meth) acrylic resin having an alicyclic structure contains at least a polymer component having an alicyclic structure as a polymer component. As the polymer component having an alicyclic structure in the polymer component of the (meth) acrylic resin having an alicyclic structure, an alicyclic alkyl ester of (meth) acrylic acid (for example, an ester of (meth) acrylic acid and an alcohol having an alicyclic structure having a carbon number of 3 or more and 9 or less) can be cited, and specifically, cyclohexyl (meth) acrylate and the like can be cited.

[0101] The (meth) acrylic resin having an alicyclic structure may also be a copolymer of a polymer component having an alicyclic structure and a polymer component not having an alicyclic structure. As the polymer component not having an alicyclic structure, a lower alkyl ester of (meth) acrylic acid (for example, a (meth) acrylic acid alkyl ester having an alkyl carbon number of 1 or more and 9 or less) is preferred, and specifically, methyl (meth) acrylate, ethyl (meth) acrylate, propyl (meth) acrylate, butyl (meth) acrylate, hexyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, etc. may be cited. These monomers may be used alone or in combination of two or more.

[0102] The (meth)acrylic resin having an alicyclic structure preferably contains cyclohexyl (meth)acrylate as a polymerized component. The content of the monomer unit derived from cyclohexyl (meth)acrylate contained in the (meth)acrylic resin having an alicyclic structure is preferably 75% by mass or more and 100% by mass or less, more preferably 85% by mass or more and 100% by mass or less, and further preferably 95% by mass or more and 100% by mass or less, relative to the total mass of the (meth)acrylic resin having an alicyclic structure.

[0103] From the viewpoint of suppressing uneven density, the resin contained in the specific resin composition preferably contains a resin having a nitrogen atom. It is believed that the specific resin composition contains a resin having a nitrogen atom, so that the charge imparting property in a high humidity environment is improved, and the generation of uneven density of the image caused by low charging in a high temperature and high humidity environment is suppressed.

[0104] Examples of the resin having a nitrogen atom include (meth)acrylic resins having a nitrogen atom obtained by polymerizing dimethylaminoethyl (meth)acrylate, dimethylacrylamide, acrylonitrile, etc.; amino resins such as urea, melamine, guanamine, and aniline; amide resins; polyurethane resins; copolymers of the above resins, etc. Among them, from the viewpoint of further suppressing uneven density of an image, the resin having a nitrogen atom is preferably a (meth)acrylic resin having a nitrogen atom, more preferably a (meth)acrylic resin having an amino group, and even more preferably a polymer containing dimethylaminoethyl (meth)acrylate as a polymerization component.

[0105] When the resin contained in the specific resin composition includes a resin having a nitrogen atom, it is preferred to further contain a resin having no nitrogen atom from the viewpoint of suppressing the environmental difference of the image density. By further containing a resin having no nitrogen atom, moisture can be appropriately adsorbed, and in particular, the increase of charge under low humidity can be prevented, thereby suppressing the environmental difference of the image density.

[0106] The resin having no nitrogen atom may be any of the specific examples of the resins described above, preferably a (meth)acrylic resin having no nitrogen atom, more preferably a (meth)acrylic resin having no nitrogen atom and having an alicyclic structure, and still more preferably a polymer containing cyclohexyl (meth)acrylate as a polymerization component.

[0107] When the specific resin composition contains both a resin having a nitrogen atom and a resin not having a nitrogen atom, the resin having a nitrogen atom is contained in an amount of preferably 0.2% by mass or more and 5.0% by mass or less, and more preferably 0.3% by mass or more and 3.0% by mass or less, relative to the total mass of the resins in the specific resin composition.

[0108] From the viewpoint of adhesion to magnetic particles, the weight average molecular weight of the resin contained in the specific resin composition is preferably less than 300,000, more preferably less than 250,000, further preferably 5,000 or more and less than 250,000, and particularly preferably 10,000 or more and 200,000 or less.

[0109] Here, the weight average molecular weight is measured by gel permeation chromatography (GPC). The molecular weight measurement based on GPC is performed using a Tosoh GPC·HLC-8120 as a measuring device, a Tosoh chromatographic column TSKgel Super HM-M (15 cm), and a THF solvent. The weight average molecular weight is calculated using a molecular weight calibration curve prepared from a monodisperse polystyrene standard sample based on the measurement results.

[0110] (Conductive particles)

[0111] The specific resin composition may contain conductive particles as other components in addition to the specific inorganic particles and the resin. The conductivity of the conductive particles means that the volume resistivity at 20° C. is less than 1×10 7 Ω·cm.

[0112] However, it is preferred that the specific resin composition does not contain conductive particles; or contains conductive particles, and in the cross section of the specific resin composition, the ratio of the total area of ​​the conductive particles to the total area of ​​the specific inorganic particles is 0.005 or less. Hereinafter, the ratio of the total area SC of the conductive particles in the cross section of the specific resin composition to the total area SP of the specific inorganic particles is also referred to as the area ratio (SC / SP). The area ratio (SC / SP) is preferably greater than 0 and less than 0.005, and more preferably greater than 0 and less than 0.004.

[0113] When the area ratio (SC / SP) is below the upper limit, the number of highly conductive components present in the internal voids of the magnetic particles is small, and the dielectric constant of the carrier as a whole tends to be lowered. It is believed that this improves the responsiveness to the AC voltage and suppresses the generation of uneven density of images formed by a development method applying an AC voltage in a high temperature and high humidity environment.

[0114] Furthermore, when the carrier of the present embodiment has a resin coating layer described later, from the viewpoint of adjusting the resistance of the carrier while suppressing concentration unevenness, it is preferred that the resin coating layer contains conductive particles and the area ratio (SC / SP) in the specific resin composition is within the above range.

[0115] Examples of the conductive particles include carbon black and inorganic particles other than carbon black (for example, titanium oxide) having conductivity.

[0116] The number average particle size of the conductive particles is, for example, in the range of 20 nm to 100 nm, preferably 30 nm to 80 nm, and more preferably 30 nm to 50 nm.

[0117] (Configuration within internal space)

[0118] As a method for configuring a specific resin composition in the internal voids of magnetic particles, for example, a method of using a resin liquid for configuring a specific resin composition obtained by dissolving or dispersing the resin, specific inorganic particles, and other components contained in the specific resin composition in a solvent can be cited. Specifically, for example, a method of mixing and stirring a resin liquid for configuring a specific resin composition and magnetic particles having internal voids under a high temperature (e.g., 75° C. or higher and 95° C. or lower) and a reduced pressure (e.g., a gauge pressure of -96 kPa or higher and -81 kPa or lower) environment can be cited.

[0119] When the carrier has a resin coating layer described below, the specific resin composition may be disposed in the internal space while forming the resin coating layer using the resin solution for forming the resin coating layer described below as the resin solution for disposing the specific resin composition.

[0120] <Resin coating>

[0121] The carrier of the present embodiment may further include a resin coating layer that covers the magnetic particles having a specific resin composition arranged in internal spaces.

[0122] In this embodiment, the resin coating layer contains inorganic particles and a specific resin composition is arranged in the internal gaps of the magnetic particles, thereby suppressing the adhesion of the electrostatic charge image developing carrier to the image retaining body when forming high-density images continuously for a long time under high temperature and high humidity.

[0123] If an image with a high image density is continuously formed for a long period of time, a large mechanical load is applied to the carrier due to the agitation in the developing device, which may cause peeling of the resin coating layer, cracks and notches of the magnetic particles. If peeling of the resin coating layer, cracks and notches of the magnetic particles occur, the magnetic particles are exposed, and thus, charge injection into the carrier is likely to occur, especially under high temperature and high humidity conditions (for example, under an environment of 28°C and 85% RH), and the carrier is likely to adhere to the image holder due to the charge.

[0124] In contrast, the resin coating layer has a high hardness and a high strength due to the filler effect of the inorganic particles contained in the resin coating layer, and the resin coating layer has a high adhesion and high strength due to the anchoring effect of the specific resin composition entering the internal gap, and the strength of the magnetic particles themselves is also improved. In addition, it is speculated that the peeling of the resin coating layer, cracks and gaps of the magnetic particles are suppressed, and the charge injection under high temperature and high humidity caused by the exposure of the magnetic particles is suppressed, and the adhesion of the carrier to the image holder due to the charge is suppressed.

[0125] More preferably, the specific resin composition existing in the internal voids of the magnetic particles is connected to the resin coating layer covering the surface of the magnetic particles. The specific resin composition is connected to the resin coating layer, thereby further suppressing the peeling of the resin coating layer and suppressing the adhesion of the carrier to the image holder.

[0126] The resin coating layer preferably contains a resin contained in a specific resin composition and specific inorganic particles.

[0127] The resin coating layer may also contain other components. The inorganic particles contained in the specific resin composition and the inorganic particles contained in the resin coating layer are preferably of the same type. Specifically, it is preferred that the specific resin composition and the resin coating layer contain inorganic particles having the same material and surface treatment method. In addition, the resin contained in the specific resin composition and the resin contained in the resin coating layer are preferably of the same type. Specifically, it is preferred that the specific resin composition and the resin coating layer contain resins having the same main skeleton.

[0128] Among them, the inorganic particles contained in the specific resin composition and the resin coating layer preferably include silica particles. That is, preferably, both the inorganic particles contained in the specific resin composition and the inorganic particles contained in the resin coating layer contain silica. By including silica particles as the inorganic particles contained in the specific resin composition and the resin coating layer, the change of image density when the image with high image density is continuously formed for a long time under high temperature and high humidity is suppressed. The reason is uncertain, but it is speculated that it is because the specific resin composition and the resin coating layer contain silica particles, which makes it easy to maintain the charging characteristics of the carrier.

[0129] It is believed that when the number average particle size of the inorganic particles is within the above range, the filler effect generated by the inorganic particles contained in the resin coating layer and the anchoring effect generated by the inorganic particles contained in the specific resin composition are easily obtained, thereby suppressing the attachment of the carrier to the image holder. In addition, it is believed that when the number average particle size of the inorganic particles is below the above upper limit value, the inorganic particles easily enter the internal voids of the magnetic particles, and the anchoring effect generated by the inorganic particles entering the internal voids is easily obtained, thereby suppressing the attachment of the carrier to the image holder.

[0130] From the viewpoint of improving the affinity with the inorganic particles and obtaining the filler effect and anchoring effect thereof, in particular, from the viewpoint of obtaining high hardness, the resin coating layer preferably contains a (meth) acrylic resin having an alicyclic structure. The (meth) acrylic resin having an alicyclic structure contains at least a polymer component having an alicyclic structure as a polymer component. As the polymer component having an alicyclic structure in the polymer component of the (meth) acrylic resin having an alicyclic structure, alicyclic alkyl esters of (meth) acrylic acid (for example, esters of (meth) acrylic acid and alcohols having an alicyclic structure having a carbon number of 3 or more and 9 or less) can be cited, specifically, cyclohexyl (meth) acrylate, etc. can be cited. The details of the resin and specific inorganic particles contained in the resin coating layer are as described above.

[0131] From the viewpoint of allowing the resin coating layer to appropriately penetrate the internal voids, the content of the specific inorganic particles contained in the resin coating layer is preferably greater than 10 mass % and less than 60 mass %, more preferably greater than 15 mass % and less than 55 mass %, and further preferably greater than 20 mass % and less than 50 mass %, relative to the total mass of the resin coating layer.

[0132] The amount of inorganic particles contained in the specific resin composition is preferably an amount in which the ratio of the total area of ​​the inorganic particles contained in the specific resin composition to the overall area of ​​the specific resin composition (hereinafter also referred to as "area ratio B") is 0.5% or more and 15% or less. In addition, the area ratio B is more preferably 1% or more and 12% or less, and further preferably 2% or more and 10% or less.

[0133] It is believed that by making the area ratio B above the above lower limit, the anchoring effect produced by the inorganic particles contained in the specific resin composition is easily obtained, and the attachment of the carrier to the image retaining body is suppressed. In addition, by making the area ratio B below the above upper limit, the elasticity of the resin contained in the specific resin composition makes it easy to ease the mechanical load, suppress cracks, notches, etc. of the magnetic particles, and suppress the attachment of the carrier to the image retaining body.

[0134] The area ratio B is obtained by analyzing the cross-sections of 100 specific resin compositions contained in the internal voids of the magnetic particles in the same manner as the confirmation method for configuring a specific resin composition in the internal voids of the magnetic particles described above. Specifically, the total area of ​​the specific resin composition as a whole and the area of ​​the inorganic particles contained in the specific resin composition in the 100 specific resin compositions are obtained to calculate the area ratio B.

[0135] The amount of inorganic particles contained in the resin coating layer is preferably an amount in which the ratio of the total area of ​​the inorganic particles contained in the resin coating layer to the overall area of ​​the resin coating layer (hereinafter also referred to as "area ratio A") is 10% or more and 50% or less. In addition, the area ratio A is more preferably 20% or more and 45% or less, and further preferably 25% or more and 40% or less.

[0136] It is believed that when the area ratio A is greater than the above lower limit, the filler effect generated by the inorganic particles contained in the resin coating layer is easily obtained, and the adhesion of the carrier to the image holder is suppressed. In addition, it is believed that when the area ratio A is less than the above upper limit, the strength of the resin coating layer is improved by the adhesive force of the resin contained in a large amount in the resin coating layer, and the peeling of the resin coating layer is suppressed, thereby suppressing the adhesion of the carrier to the image holder.

[0137] The area ratio A is obtained by analyzing the cross section of 100 carriers in the same manner as the method for confirming the internal voids in the magnetic particles described above. Specifically, the total area of ​​the resin coating layer in the cross section of each particle, the area of ​​the entire resin coating layer, and the area of ​​the inorganic particles contained in the resin coating layer are obtained to calculate the area ratio A.

[0138] From the viewpoint of suppressing the adhesion of the carrier to the image retaining body, the above-mentioned area ratio A and area ratio B preferably satisfy the relationship of area ratio A>area ratio B. In particular, from the viewpoint of suppressing the adhesion of the carrier to the image retaining body, it is more preferred that the area ratio A is within the above-mentioned range and the area ratio A>area ratio B.

[0139] By making the area ratio A>area ratio B, the filler effect generated by the inorganic particles contained in the resin coating layer is obtained, and the reduction of the anchoring effect caused by too little resin of the specific resin composition entering the internal gaps of the magnetic particles is suppressed. In other words, it is believed that both the filler effect and the anchoring effect are efficiently obtained, and the adhesion of the carrier to the image holder is suppressed.

[0140] From the viewpoint of suppressing the adhesion of the carrier to the image retaining body, the area ratio B is preferably more than 0.05 times and less than 0.3 times of the area ratio A. That is, the value of the area ratio B / area ratio A is preferably more than 0.05 and less than 0.3. The value of the area ratio B / area ratio A is more preferably more than 0.07 and less than 0.25, and further preferably more than 0.1 and less than 0.2. It is believed that by the value of the area ratio B / area ratio A being more than the above-mentioned lower limit, it is easy to obtain the anchoring effect produced by the inorganic particles contained in the specific resin composition, and the adhesion of the carrier to the image retaining body is suppressed. In addition, it is believed that by the value of the area ratio B / area ratio A being less than the above-mentioned upper limit, the reduction of the anchoring effect caused by the resin of the specific resin composition entering the internal gap of the magnetic particles is suppressed, and the adhesion of the carrier to the image retaining body is suppressed.

[0141] From the viewpoint of controlling the resistance, the resin coating layer preferably contains the above-mentioned conductive particles. The details of the conductive particles contained in the resin coating layer are as described above.

[0142] From the viewpoint of appropriate resistance value, the content of the conductive particles contained in the resin coating layer is preferably 0.5 mass % to 15 mass %, more preferably 2 mass % to 10 mass %, and further preferably 3 mass % to 8 mass %, relative to the total mass of the resin coating layer.

[0143] The resin coating layer may contain other components as necessary.

[0144] As other components, for example, nitrogen-containing resin particles and inorganic particles other than specific inorganic particles can be mentioned.

[0145] There is an advantage that the charging speed is improved by containing nitrogen-containing resin particles in the resin coating layer.

[0146] Examples of the nitrogen-containing resin particles include (meth) acrylic resins containing dimethylaminoethyl (meth)acrylate, dimethylacrylamide, acrylonitrile, etc. and polymerized therefrom; amino resins such as urea, melamine, guanamine, and aniline; amide resins; polyurethane resins; and copolymers of the above resins. When the resin coating layer contains the nitrogen-containing resin particles, the content of the nitrogen-containing resin particles is preferably 5% by mass or more and 20% by mass or less, more preferably 8% by mass or more and 16% by mass or less, and even more preferably 9% by mass or more and 14% by mass or less, relative to the total mass of the resin coating layer, from the viewpoint of improving the charging speed and the ease of introduction into the coating layer.

[0147] As inorganic particles other than specific inorganic particles, for example, there can be mentioned particles of metal oxides such as titanium oxide (titanium dioxide), barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, chromium oxide, cerium oxide, antimony trioxide, magnesium oxide, and zirconium oxide; particles of metal compounds such as barium sulfate, barium carbonate, aluminum borate, and potassium titanate; particles of metals such as gold, silver, and copper, etc.

[0148] In the present embodiment, carbon black is considered not to be an inorganic particle. In the case where the resin coating layer contains inorganic particles other than specific inorganic particles, from the viewpoint of reducing the relative dielectric constant of the entire carrier and suppressing concentration unevenness, the content of inorganic particles other than specific inorganic particles relative to the total mass of the resin coating layer is preferably 0.1 mass % or less.

[0149] From the viewpoint of electrical resistance and charging performance, the average thickness of the resin coating layer is preferably 0.6 μm to 1.4 μm, more preferably 0.8 μm to 1.2 μm, particularly preferably 0.8 μm to 1.1 μm.

[0150] The average thickness of the resin coating layer is obtained by analyzing the cross section of 100 carriers in the same manner as the method for confirming the internal voids in the magnetic particles described above. Specifically, the thickness of the resin coating layer at nine locations in the cross section of each particle is obtained, and the thickness of each of the nine locations in the 100 particles is averaged, and the obtained value is set as the average thickness of the resin coating layer.

[0151] As a method for forming a resin coating layer on the surface of magnetic particles, for example, a wet method and a dry method can be cited. The wet method is a method using a solvent that dissolves or disperses the resin constituting the resin coating layer. On the other hand, the dry method is a method that does not use the above solvent.

[0152] As wet production methods, for example, there can be cited an immersion method in which the magnetic particles are immersed in a resin liquid for forming a resin coating layer to coat the particles, a spray method in which the resin liquid for forming a resin coating layer is sprayed on the surface of the magnetic particles, a fluidized bed method in which the resin liquid for forming a resin coating layer is sprayed on the magnetic particles in a fluidized state in a fluidized bed, a kneading coating method in which the magnetic particles and the resin liquid for forming a resin coating layer are mixed in a kneading coater and the solvent is removed, etc. These production methods may be repeated or combined.

[0153] The resin, inorganic particles and other components are dissolved or dispersed in a solvent to prepare a resin solution for forming a resin coating layer used in a wet method. The solvent is not particularly limited, and for example, aromatic hydrocarbons such as toluene and xylene; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane are used.

[0154] As a dry method, for example, a method of heating a mixture of magnetic particles and a resin for forming a resin coating layer in a dry state to form a resin coating layer can be cited. Specifically, for example, magnetic particles and a resin for forming a resin coating layer are mixed in a gas phase and heated and melted to form a resin coating layer.

[0155] The formation of the resin coating layer may be performed simultaneously with the above-mentioned step of disposing the specific resin composition in the internal voids of the magnetic particles, or may be performed separately from the disposition of the specific resin composition. In the case where the formation of the resin coating layer is performed separately from the disposition of the specific resin composition, for example, the formation of the resin coating layer is performed by the above-mentioned method using magnetic particles in which the specific resin composition is disposed in the internal voids.

[0156] Specifically, for example, a method can be mentioned in which a first resin liquid having low concentrations of inorganic particles and resin is used, the first resin liquid is mixed with magnetic particles, and then a second resin liquid having higher concentrations of inorganic particles and resin than the first resin liquid is added and mixed. In this method, in the process of mixing the first resin liquid with the magnetic particles, the inorganic particles and resin easily enter the internal voids of the magnetic particles, and then, in the process of adding and mixing the second resin liquid, a resin coating layer is easily formed. Therefore, it is easy to obtain a carrier in which a specific resin composition is arranged in the internal voids of the magnetic particles and a resin coating layer is formed on the surface of the magnetic particles.

[0157] As an example of a method for disposing a specific resin composition and forming a resin coating layer, a method having a first step of mixing a first resin liquid and magnetic particles, and a second step of adding a second resin liquid to the mixture of the first resin liquid and the magnetic particles and further mixing them is described below.

[0158] The first resin liquid and the second resin liquid are prepared by dissolving or dispersing the resin, the inorganic particles, and other components used as necessary in a solvent as described above.

[0159] The solvent is not particularly limited, and for example, aromatic hydrocarbons such as toluene and xylene, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran and dioxane, etc. can be used. The solvent contained in the first resin liquid and the solvent contained in the second resin liquid may be the same or different, but are preferably the same.

[0160] The concentration of the inorganic particles in the first resin liquid is, for example, in the range of 0.05 mass % to 10 mass % based on the entire resin liquid, preferably 0.07 mass % to 5 mass %, and more preferably 0.1 mass % to 3 mass %.

[0161] The concentration of the inorganic particles in the second resin liquid is, for example, in the range of 1 mass % to 20 mass % inclusive, preferably 2 mass % to 15 mass % inclusive, and more preferably 3 mass % to 10 mass % inclusive, based on the entire resin liquid.

[0162] The concentration of the inorganic particles in the first resin liquid is preferably 0.01 to 0.8 times, more preferably 0.02 to 0.6 times, and even more preferably 0.03 to 0.4 times the concentration of the inorganic particles in the second resin liquid.

[0163] The concentration of the resin in the first resin liquid is, for example, in the range of 0.5% by mass to 20% by mass, preferably 1% by mass to 15% by mass, and more preferably 2% by mass to 10% by mass, relative to the entire resin liquid.

[0164] The concentration of the resin in the second resin liquid is, for example, in the range of 3% by mass to 30% by mass, preferably 4% by mass to 25% by mass, and more preferably 5% by mass to 20% by mass, relative to the entire resin liquid.

[0165] The concentration of the resin in the first resin liquid is preferably 0.1 to 0.9 times, more preferably 0.2 to 0.8 times, and even more preferably 0.3 to 0.7 times the concentration of the resin in the second resin liquid.

[0166] The viscosity of the first resin liquid at 25° C. is, for example, in the range of 5 mPa·s to 50 mPa·s, preferably 10 mPa·s to 40 mPa·s, and more preferably 12 mPa·s to 30 mPa·s.

[0167] The viscosity of the second resin liquid at 25° C. is, for example, in the range of 30 mPa·s to 120 mPa·s, preferably 35 mPa·s to 100 mPa·s, and more preferably 40 mPa·s to 80 mPa·s.

[0168] The viscosity of the first resin liquid at 25° C. is preferably 0.05 to 0.6 times, more preferably 0.1 to 0.5 times, and even more preferably 0.2 to 0.4 times the viscosity of the second resin liquid at 25° C.

[0169] The viscosity of the resin liquid at 25° C. was measured as follows: Specifically, the viscosity was measured by immersing the detection terminal in the resin liquid using a vibration type viscometer.

[0170] Examples of the conditions in the first step include a temperature of 30° C. to 70° C., a time of 10 minutes to 60 minutes, and a pressure (gauge pressure) of −30 kPa to 0 kPa.

[0171] Examples of the conditions in the second step include a temperature of 70° C. to 90° C., a time of 10 minutes to 120 minutes, and a pressure (gauge pressure) of -95 kPa to -70 kPa.

[0172] The method having the first step and the second step may further include other steps as necessary. Examples of other steps include a step of removing the solvent after the second step, and a step of removing fine powder and coarse powder of the obtained particles.

[0173] The exposed area ratio of the magnetic particles on the carrier surface is preferably 5% or more and 30% or less, more preferably 7% or more and 25% or less, and further preferably 10% or more and 25% or less. The exposed area ratio of the magnetic particles in the carrier can be controlled by the amount of resin used to form the resin coating layer. The greater the amount of resin relative to the amount of magnetic particles, the smaller the exposed area ratio.

[0174] The exposed area ratio of the magnetic particles on the carrier surface is a value obtained by the following method.

[0175] A carrier as a target and magnetic particles from which a resin coating layer is removed from the carrier as a target are prepared. As a method for removing the resin coating layer from the carrier, for example, a method of removing the resin coating layer by dissolving the resin component with an organic solvent, a method of removing the resin coating layer by heating at about 800°C to make the resin component disappear, etc. The carrier and the magnetic particles are respectively used as measurement samples, and the Fe concentration (atomic %) on the surface of the sample is quantified by XPS, and (Fe concentration of the carrier) ÷ (Fe concentration of the magnetic particles) × 100 is calculated, and the obtained value is set as the exposed area ratio (%) of the magnetic particles.

[0176] From the viewpoint of forming a moderate adhesion between the toner and the carrier to obtain a sufficient amount of toner development, and obtaining an appropriate magnetic brush to form an image with excellent fine line reproducibility, the number average particle size of the carrier is preferably 15 μm or more and 100 μm or less, more preferably 20 μm or more and 80 μm or less, and particularly preferably 25 μm or more and 40 μm or less. The number average particle size of the carrier is obtained by the same method as the number average particle size of the magnetic particles described above.

[0177] [Electrostatic image developer]

[0178] The developer of the present embodiment is a two-component developer including the electrostatic charge image developing carrier of the present embodiment and a toner. The toner includes toner particles and, if necessary, an external additive.

[0179] The mixing ratio (mass ratio) of the carrier and the toner in the developer is preferably carrier:toner=100:1 to 100:30, more preferably 100:3 to 100:20.

[0180] <Toner particles>

[0181] The toner particles contain, for example, a binder resin and, if necessary, a colorant, a release agent, and other additives.

[0182] -Bonding resin-

[0183] Examples of the binder resin include: homopolymers of monomers such as styrenes (e.g., styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers formed by combining two or more of these monomers.

[0184] Examples of the binder resin include epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, modified rosins and other non-vinyl resins, mixtures thereof with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the presence of the non-vinyl resins.

[0185] These binder resins may be used alone or in combination of two or more.

[0186] As the binder resin, polyester resin is preferred.

[0187] As the polyester resin, for example, a known amorphous polyester resin can be cited. The polyester resin can also be used together with a crystalline polyester resin. However, the crystalline polyester resin is preferably used in a range of 2% by mass or more and 40% by mass or less (preferably 2% by mass or more and 20% by mass or less) relative to the total binding resin.

[0188] The "crystallinity" of a resin means that in differential scanning calorimetry (DSC), it does not show a step-like change in endothermic value but has a clear endothermic peak. Specifically, it means that the half-value width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min).

[0189] On the other hand, the "amorphous" nature of a resin means that the half value width exceeds 10°C, indicating a step-like change in the endothermic value, or no clear endothermic peak is observed.

[0190] Amorphous polyester resin

[0191] Examples of the non-crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the non-crystalline polyester resin, a commercially available product may be used, and a synthetic non-crystalline polyester resin may also be used.

[0192] Examples of the polycarboxylic acid include: aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.); alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.); aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.); anhydrous products thereof, or lower (e.g., carbon number of 1 to 5) alkyl esters thereof. Among these, the polycarboxylic acid is preferably, for example, an aromatic dicarboxylic acid.

[0193] The polycarboxylic acid may be used together with the dicarboxylic acid, and a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrous forms thereof, or lower (e.g., having 1 to 5 carbon atoms) alkyl esters thereof.

[0194] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0195] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among them, the polyol is preferably, for example, an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.

[0196] As the polyol, a trivalent or higher polyol having a cross-linked structure or a branched structure may be used together with a diol. Examples of the trivalent or higher polyol include glycerin, trimethylol propane, and pentaerythritol.

[0197] The polyols may be used alone or in combination of two or more.

[0198] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower.

[0199] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), and more specifically, by "extrapolating the glass transition start temperature" described in the method for determining the glass transition temperature in JIS K7121:1987 "Methods for determining transition temperatures of plastics".

[0200] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less.

[0201] The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less.

[0202] The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.

[0203] The weight average molecular weight and the number average molecular weight were measured by gel permeation chromatography (GPC). The molecular weight measurement based on GPC was performed using a Tosoh GPC·HLC-8120GPC as a measuring device, a Tosoh chromatographic column TSKgel SuperHM-M (15 cm), and a THF solvent. The weight average molecular weight and the number average molecular weight were calculated using a molecular weight calibration curve prepared from a monodisperse polystyrene standard sample based on the measurement results.

[0204] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the amorphous polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water and alcohol generated during condensation.

[0205] When the monomers of the raw materials are insoluble or incompatible at the reaction temperature, a high boiling point solvent may be added as a cosolvent to dissolve them. In this case, the cosolvent is distilled off while the polycondensation reaction is carried out. When there are monomers with poor compatibility in the copolymerization reaction, it is preferred to condense the monomers with poor compatibility with an acid or alcohol to be polycondensed with the monomers in advance, and then polycondense with the main component.

[0206] Crystalline polyester resin

[0207] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the crystalline polyester resin, a commercially available product may be used, and a synthetic crystalline polyester resin may also be used.

[0208] Here, in order to easily form a crystal structure, the crystalline polyester resin is preferably a polycondensate using a straight-chain aliphatic polymerizable monomer rather than a polycondensate using a polymerizable monomer having an aromatic ring.

[0209] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and 2,6-naphthalene dicarboxylic acid, etc.), anhydrous products thereof, or lower (e.g., having a carbon number of 1 to 5) alkyl esters thereof.

[0210] The polycarboxylic acid may be used together with the dicarboxylic acid, and a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrates, or their lower (e.g., carbon number 1 to 5) alkyl esters.

[0211] As the polycarboxylic acid, a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids.

[0212] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0213] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion having carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosandiol. Among them, preferred aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.

[0214] The polyol may be used together with the diol in a trivalent or higher alcohol having a cross-linked structure or a branched structure. Examples of the trivalent or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol.

[0215] The polyols may be used alone or in combination of two or more.

[0216] Here, the polyol preferably contains an aliphatic diol in an amount of 80 mol % or more, more preferably 90 mol % or more.

[0217] The melting temperature of the crystalline polyester resin is preferably 50° C. or higher and 100° C. or lower, more preferably 55° C. or higher and 90° C. or lower, and further preferably 60° C. or higher and 85° C. or lower.

[0218] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by using the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121:1987 “Methods for determining transition temperatures of plastics”.

[0219] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0220] The crystalline polyester resin can be obtained by a known production method, for example, similarly to the amorphous polyester.

[0221] The content of the binder resin is preferably 40% by mass or more and 95% by mass or less, more preferably 50% by mass or more and 90% by mass or less, and further preferably 60% by mass or more and 85% by mass or less, based on the entire toner particles.

[0222] -Colorants-

[0223] Examples of the coloring agent include carbon black, chrome yellow, Hansa yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, acid lake orange (vulcan orange), watchung red (watchung red), permanent red, brilliant carmine 3B, brilliant carmine 6B, Dupont oil red, pyrazolone red, lithotripter red, rhodamine B lake, lake red C, pigment red, Bengal rose red, aniline blue, ultramarine blue, calco oil blue (calco oil blue), etc. blue), methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate and other pigments; acridine, xanthene, azo, benzoquinone, azine, anthraquinone, thioindigo, dioxazine, thiazine, azomethine, indigo, phthalocyanine, aniline black, polymethine, triphenylmethane, diphenylmethane, thiazole and other dyes.

[0224] The coloring agent may be used alone or in combination of two or more.

[0225] The colorant may be a colorant that has been subjected to surface treatment as required, or may be used in combination with a dispersant. In addition, a plurality of colorants may be used in combination.

[0226] The content of the colorant is preferably 1% by mass or more and 30% by mass or less, and more preferably 3% by mass or more and 15% by mass or less, based on the entire toner particles.

[0227] -Release agent-

[0228] Examples of the release agent include hydrocarbon waxes, natural waxes such as palm wax, rice wax, and candelilla wax, synthetic waxes such as montan wax, or mineral / petroleum waxes, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.

[0229] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower.

[0230] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by using the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121:1987 “Methods for determining transition temperatures of plastics”.

[0231] The content of the releasing agent is preferably 1% by mass or more and 20% by mass or less, and more preferably 5% by mass or more and 15% by mass or less, based on the entire toner particles.

[0232] -Other additives-

[0233] Examples of other additives include known additives such as magnetic materials, charge control agents, and inorganic powders. These additives are contained in the toner particles as internal additives.

[0234] -Characteristics of toner particles, etc.-

[0235] The toner particles may be toner particles of a single-layer structure, or may be toner particles of a so-called core-shell structure consisting of a core portion (core particle) and a coating layer (shell layer) that covers the core portion.

[0236] The toner particles of the core-shell structure are preferably composed of, for example, a core portion including a binder resin and other additives such as a colorant and a release agent as required, and a coating layer including a binder resin.

[0237] The volume average particle diameter (D50v) of the toner particles is preferably 2 μm or more and 10 μm or less, and more preferably 4 μm or more and 8 μm or less.

[0238] The volume average particle size (D50v) of the toner particles is measured by using Coulter Multisizer II (manufactured by Beckman Coulter) and ISOTON-II (manufactured by Beckman Coulter) as the electrolyte.

[0239] In the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and then added to 100 ml to 150 ml of the electrolyte.

[0240] The electrolyte in which the sample is suspended is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with a particle size of 2 μm or more and 60 μm or less is measured using a Coulter Multisizer II with a hole having an aperture of 100 μm. The number of particles sampled is 50,000. The volume-based particle size distribution is depicted from the diameter side, and the particle size that becomes 50% cumulative is set as the volume average particle size D50v.

[0241] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.

[0242] The average circularity of the toner particles is calculated by (equivalent circle circumference) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projection image)]. Specifically, it is a value measured by the following method.

[0243] First, the toner particles to be measured are sucked and collected to form a flat flow, and the particle image is captured as a still image by instantaneous stroboscopic light. The particle image is analyzed by a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation) to obtain the average circularity. The number of samples for obtaining the average circularity is set to 3500.

[0244] When the toner has an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant and then subjected to ultrasonic treatment to obtain toner particles from which the external additive has been removed.

[0245] -Method for producing toner particles-

[0246] The toner particles can also be produced by any of dry methods (e.g., kneading and pulverization methods, etc.) and wet methods (e.g., aggregation and coalescence methods, suspension polymerization methods, dissolution and suspension methods, etc.). These methods are not particularly limited, and known methods are used. Among them, it is preferred to obtain the toner particles by the aggregation and coalescence method.

[0247] Specifically, for example, in the case of manufacturing colorant particles by the coagulation and aggregation method, the colorant particles are manufactured through the following steps: a step of preparing a resin particle dispersion in which resin particles serving as a binding resin are dispersed (resin particle dispersion preparation step); a step of aggregating resin particles (and other particles as needed) in the resin particle dispersion (in a dispersion after other particle dispersions are mixed as needed) to form agglomerated particles (agglomerated particle formation step); and a step of heating the agglomerated particle dispersion in which the agglomerated particles are dispersed to fuse / agglomerate the agglomerated particles to form colorant particles (fusion / agglomeration step).

[0248] Next, each process will be described in detail.

[0249] In the following description, a method for obtaining toner particles containing a colorant and a release agent is described, but the colorant and the release agent are used as necessary. Of course, other additives besides the colorant and the release agent may also be used.

[0250] -Resin particle dispersion preparation process-

[0251] For example, a colorant particle dispersion in which colorant particles are dispersed and a release agent particle dispersion in which release agent particles are dispersed are prepared together with a resin particle dispersion in which resin particles serving as a binder resin are dispersed.

[0252] The resin particle dispersion is prepared by, for example, dispersing the resin particles in a dispersion medium using a surfactant.

[0253] Examples of the dispersion medium used for the resin particle dispersion include aqueous media.

[0254] Examples of the aqueous medium include water such as distilled water and ion-exchanged water, and alcohols, etc. These may be used alone or in combination of two or more.

[0255] As surfactants, for example, anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols, etc. can be cited. Among them, anionic surfactants and cationic surfactants can be cited in particular. Nonionic surfactants can also be used in combination with anionic surfactants or cationic surfactants.

[0256] The surfactant may be used alone or in combination of two or more.

[0257] In the resin particle dispersion, as a method of dispersing the resin particles in the dispersion medium, for example, a general dispersion method such as a rotary shearing homogenizer, or a ball mill, a sand mill, or a DYNO-MILL having a medium can be cited. In addition, the resin particles can also be dispersed in the dispersion medium by a phase inversion emulsification method depending on the type of the resin particles. The phase inversion emulsification method refers to the following method: the resin to be dispersed is dissolved in a hydrophobic organic solvent that can dissolve the resin, and after adding a base to the organic continuous phase (O phase) for neutralization, an aqueous medium (W phase) is added, thereby performing a phase inversion from W / O to O / W, and dispersing the resin in the aqueous medium in a particle form.

[0258] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably 0.01 μm or more and 1 μm or less, more preferably 0.08 μm or more and 0.8 μm or less, and further preferably 0.1 μm or more and 0.6 μm or less.

[0259] The volume average particle size of the resin particles is measured as follows: using the particle size distribution obtained by measurement using a laser diffraction particle size distribution analyzer (e.g., LA-700 manufactured by Horiba, Ltd.), the cumulative distribution of the volume is plotted from the small particle size side for the divided particle size range (channel), and the particle size that is 50% cumulatively with respect to all particles is taken as the volume average particle size D50v. The volume average particle size of particles in other dispersions is measured in the same manner.

[0260] The content of the resin particles contained in the resin particle dispersion is preferably 5% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 40% by mass or less.

[0261] The same operation as the resin particle dispersion is performed to prepare, for example, a colorant particle dispersion and a release agent particle dispersion. That is, the volume average particle size of the particles in the resin particle dispersion, the dispersion medium, the dispersion method, and the content of the particles are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.

[0262] - Agglomerated Particle Formation Step-

[0263] Next, the resin particle dispersion, the colorant particle dispersion, and the release agent particle dispersion are mixed.

[0264] Then, in the mixed dispersion, the resin particles, the colorant particles, and the releasing agent particles are heterogeneously aggregated to form aggregated particles including the resin particles, the colorant particles, and the releasing agent particles and having a diameter close to the target toner particle diameter.

[0265] Specifically, for example, a coagulant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to be acidic (for example, a pH of 2 or more and 5 or less), and after a dispersion stabilizer is added as needed, it is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, the glass transition temperature of the resin particles is above -30°C and below the glass transition temperature of -10°C), so that the particles dispersed in the mixed dispersion are agglomerated to form agglomerated particles.

[0266] In the aggregated particle formation step, for example, while the mixed dispersion is stirred with a rotary shearing homogenizer, a coagulant is added at room temperature (e.g., 25° C.), the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 to 5), and a dispersion stabilizer is added as needed, followed by heating.

[0267] Examples of the coagulant include surfactants having opposite polarity to the surfactant contained in the mixed dispersion, inorganic metal salts, and divalent or higher metal complexes. When a metal complex is used as the coagulant, the amount of surfactant used is reduced, and the charging characteristics are improved.

[0268] If necessary, an additive that forms a complex or similar bond with the metal ion of the coagulant may be used together with the coagulant. As such an additive, a chelating agent is preferably used.

[0269] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.

[0270] As the chelating agent, a water-soluble chelating agent may also be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; and aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).

[0271] The amount of the chelating agent added is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, based on 100 parts by mass of the resin particles.

[0272] - Fusion and aggregation process -

[0273] Next, the aggregated particle dispersion containing the dispersed aggregated particles is heated to, for example, a temperature higher than the glass transition temperature of the resin particles (eg, a temperature 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to fuse / agglomerate the aggregated particles to form toner particles.

[0274] Through the above steps, toner particles are obtained.

[0275] The colorant particles can also be manufactured through the following steps: after obtaining a dispersion of agglomerated particles dispersed therein, further mixing the agglomerated particle dispersion and a resin particle dispersion dispersed therein to agglomerate the resin particles so that they further adhere to the surface of the agglomerated particles to form second agglomerated particles; and heating the second agglomerated particle dispersion in which the second agglomerated particles are dispersed therein to fuse / agglomerate the second agglomerated particles to form colorant particles with a core-shell structure.

[0276] After the fusion / agglomeration process is completed, the toner particles formed in the solution are subjected to a known washing process, a solid-liquid separation process, and a drying process to obtain the toner particles in a dry state. From the perspective of chargeability, the washing process is preferably fully subjected to displacement washing using ion exchange water. From the perspective of productivity, the solid-liquid separation process is preferably subjected to suction filtration, pressure filtration, etc. From the perspective of productivity, the drying process is preferably subjected to freeze drying, airflow drying, fluidized drying, vibration-type fluidized drying, etc.

[0277] The toner of the present embodiment is prepared, for example, by adding an external additive to the obtained dry toner particles and mixing them. The mixing is preferably performed by, for example, a V-type mixer, a Henschel mixer, a Roediger mixer, etc. Furthermore, if necessary, a vibration sieving machine, a wind sieving machine, etc. may be used to remove coarse particles of the toner.

[0278] -External Additives-

[0279] Examples of external additives include inorganic particles. Examples of the inorganic particles include SiO 2 、TiO 2 、Al 2 O 3 , CuO, ZnO, SnO 2 、CeO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O、Na 2 O、ZrO 2 、CaO·SiO 2 , K 2 O·(TiO 2 )n、Al 2 O 3 ·2SiO 2 、CaCO 3 MgCO 3 ,BaSO 4 MgSO 4 wait.

[0280] The surface of the inorganic particles as an external additive is preferably subjected to a hydrophobic treatment. The hydrophobic treatment is performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, a silane coupling agent, silicone oil, a titanate coupling agent, an aluminum coupling agent, etc. can be cited. These can be used alone or in combination of two or more.

[0281] Usually, the amount of the hydrophobizing agent is, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.

[0282] Examples of the external additives include resin particles (polystyrene, polymethyl methacrylate, melamine resin, etc.), detergent active agents (for example, metal salts of higher fatty acids represented by zinc stearate, and particles of fluorine-based high molecular weight bodies), and the like.

[0283] The amount of the external additive added is preferably 0.01% by mass or more and 5% by mass or less, and more preferably 0.01% by mass or more and 2.0% by mass or less, based on the toner particles.

[0284] <Image forming apparatus, image forming method>

[0285] The image forming device of the present embodiment comprises: an image holder; a charging device for charging the surface of the image holder; an electrostatic charge image forming device for forming an electrostatic charge image on the surface of the charged image holder; a developing device for storing an electrostatic charge image developer and developing the electrostatic charge image formed on the surface of the image holder into a toner image by the electrostatic charge image developer; a transfer device for transferring the toner image formed on the surface of the image holder to the surface of a recording medium; and a fixing device for fixing the toner image transferred to the surface of the recording medium. Furthermore, the electrostatic charge image developer of the present embodiment is used as the electrostatic charge image developer.

[0286] In the image forming device of the present embodiment, an image forming method (the image forming method of the present embodiment) is implemented, and the image forming method has: a charging process for charging the surface of an image retaining body; an electrostatic charge image forming process for forming an electrostatic charge image on the surface of the charged image retaining body; a developing process for developing the electrostatic charge image formed on the surface of the image retaining body into a colorant image by the electrostatic charge image developer of the present embodiment; a transfer process for transferring the colorant image formed on the surface of the image retaining body to the surface of a recording medium; and a fixing process for fixing the colorant image transferred to the surface of the recording medium.

[0287] The image forming device of this embodiment applies the following well-known image forming devices: a direct transfer device that directly transfers the colorant image formed on the surface of the image retaining body to the recording medium; an intermediate transfer device that transfers the colorant image formed on the surface of the image retaining body to the surface of the intermediate transfer body for the first time, and transfers the colorant image transferred to the surface of the intermediate transfer body to the surface of the recording medium for the second time; a cleaning device having a cleaning unit that cleans the surface of the image retaining body after the transfer of the colorant image and before charging; a de-static device having a de-static unit that de-staticizes the surface of the image retaining body by irradiating de-static light to remove static electricity after the transfer of the colorant image and before charging, etc.

[0288] In the case where the image forming device of the present embodiment is an intermediate transfer type device, the transfer device, for example, has the following structure: an intermediate transfer body on the surface of which the colorant image is transferred, a primary transfer device that transfers the colorant image formed on the surface of the image retaining body to the surface of the intermediate transfer body for the first time, and a secondary transfer device that transfers the colorant image transferred to the surface of the intermediate transfer body for the second time to the surface of the recording medium.

[0289] In the image forming apparatus of this embodiment, for example, the portion including the developing device may be a cartridge structure (processing cartridge) that is detachable from the image forming apparatus. As the processing cartridge, for example, a processing cartridge that contains the electrostatic image developer of this embodiment and includes the developing device is preferably used.

[0290] An example of the image forming apparatus according to the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and the description of the others is omitted.

[0291] Figure 2 It is a diagram schematically showing the structure of the image forming apparatus according to the present embodiment.

[0292] Figure 2 The image forming apparatus shown in the figure has first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming units) of an electronic photographic method, and each image forming unit outputs images of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter, sometimes referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel with each other at a predetermined distance in the horizontal direction. These units 10Y, 10M, 10C, and 10K may also be process cartridges that are attached to and detached from the image forming apparatus.

[0293] Above each unit 10Y, 10M, 10C, 10K, an intermediate transfer belt (an example of an intermediate transfer body) 20 is extended through each unit. The intermediate transfer belt 20 is wound around a driving roller 22 and a supporting roller 24, and travels in a direction from the first unit 10Y toward the fourth unit 10K. The supporting roller 24 is biased in a direction away from the driving roller 22 by a spring (not shown), etc., and tension is applied to the intermediate transfer belt 20 wound around the intermediate transfer belt 20. An intermediate transfer body cleaning device 30 is provided on the image holding body side of the intermediate transfer belt 20, which is opposite to the driving roller 22.

[0294] Yellow, magenta, cyan, and black toners stored in toner cartridges 8Y, 8M, 8C, and 8K are supplied to the developing devices 4Y, 4M, 4C, and 4K of the respective units 10Y, 10M, 10C, and 10K, respectively.

[0295] The first to fourth units 10Y, 10M, 10C, and 10K have similar structures and operations, and therefore the first unit 10Y disposed on the upstream side in the traveling direction of the intermediate transfer belt and forming a yellow image will be described as a representative.

[0296] The first unit 10Y has a photoreceptor 1Y that functions as an image holder. The following are arranged in order around the photoreceptor 1Y: a charging roller (an example of a charging device) 2Y that charges the surface of the photoreceptor 1Y to a preset potential; an exposure device (an example of an electrostatic image forming device) 3 that forms an electrostatic image by exposing the charged surface to laser light 3Y based on a color-decomposed image signal; a developing device 4Y that supplies charged toner to the electrostatic image and develops the electrostatic image; a primary transfer roller 5Y (an example of a primary transfer device) that transfers the developed toner image to the intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning device) 6Y that removes the toner remaining on the surface of the photoreceptor 1Y after the primary transfer.

[0297] The primary transfer roller 5Y is arranged inside the intermediate transfer belt 20 and is provided at a position opposite to the photoreceptor 1Y. A bias power supply (not shown) for applying a primary transfer bias is connected to each of the primary transfer rollers 5Y, 5M, 5C, and 5K of each unit. Each bias power supply changes the value of the transfer bias applied to each primary transfer roller based on control by a control unit (not shown).

[0298] Next, the operation of forming a yellow image in the first unit 10Y will be described.

[0299] First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.

[0300] The photoreceptor 1Y is conductive (e.g., a volume resistivity of 1×10-6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate with a resistance of 100 Ωcm or less. The photosensitive layer is usually high in resistance (resistance of a general resin), but has a property that when irradiated with laser light, the specific resistance of the portion irradiated with the laser light changes. Then, according to the image data for yellow sent from the control unit (not shown), the laser light 3Y is irradiated from the exposure device 3 to the surface of the charged photoreceptor 1Y. As a result, an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0301] The electrostatic charge image refers to an image formed on the surface of the photoreceptor 1Y by charging, and is a so-called negative latent image formed as follows: due to the laser light 3Y, the resistivity of the irradiated portion of the photosensitive layer is reduced, and the charged charges on the surface of the photoreceptor 1Y flow, while on the other hand, the charges on the portion not irradiated by the laser light 3Y remain.

[0302] The electrostatic charge image formed on the photoreceptor 1Y rotates to a preset development position as the photoreceptor 1Y travels. Then, at the development position, the electrostatic charge image on the photoreceptor 1Y is developed into a toner image by the developing device 4Y and visualized.

[0303] In the developing device 4Y, for example, an electrostatic charge image developer including at least a yellow colorant and a carrier is accommodated. The yellow colorant is frictionally charged by being stirred inside the developing device 4Y, and has a charge of the same polarity (negative polarity) as the charge charged to the photoreceptor 1Y and is retained on a developer roller (an example of a developer retainer). Then, the surface of the photoreceptor 1Y passes through the developing device 4Y, whereby the yellow colorant is electrostatically attached to the latent image portion on the surface of the photoreceptor 1Y that has been de-charged, and the latent image is developed by the yellow colorant. The photoreceptor 1Y on which the yellow colorant image is formed continues to travel at a preset speed, and the toner image developed on the photoreceptor 1Y is conveyed to a preset primary transfer position.

[0304] When the yellow toner image on the photoreceptor 1Y is conveyed to the primary transfer position, a primary transfer bias is applied to the primary transfer roller 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred to the intermediate transfer belt 20. The transfer bias applied at this time is a (+) polarity opposite to the polarity (-) of the toner, and is controlled by a control section (not shown) in the first unit 10Y to, for example, +10 μA.

[0305] On the other hand, the toner remaining on the photoreceptor 1Y is removed and recovered by the photoreceptor cleaning device 6Y.

[0306] The primary transfer bias applied to the primary transfer rollers 5M, 5C, 5K after the second unit 10M is also controlled in accordance with the first unit.

[0307] In this way, the intermediate transfer belt 20 to which the yellow toner image is transferred in the first unit 10Y is sequentially conveyed through the second to fourth units 10M, 10C, and 10K, and the toner images of the respective colors are overlapped and multi-transferred.

[0308] The intermediate transfer belt 20 to which the toner images of four colors are multi-transferred by the first to fourth units arrives at the secondary transfer section, which is composed of the intermediate transfer belt 20, the support roller 24 in contact with the inner surface of the intermediate transfer belt, and the secondary transfer roller (an example of a secondary transfer device) 26 arranged on the image holding surface side of the intermediate transfer belt 20. On the other hand, the recording paper (an example of a recording medium) P is supplied to the gap between the secondary transfer roller 26 and the intermediate transfer belt 20 at a preset timing via a supply mechanism, and a secondary transfer bias is applied to the support roller 24. The transfer bias applied at this time has the same polarity (-) as the polarity (-) of the toner, and the electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, and the toner image on the intermediate transfer belt 20 is transferred to the recording paper P. The secondary transfer bias at this time is determined based on the resistance detected by the resistance detection unit (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.

[0309] Thereafter, the recording paper P is fed into a pressure-contact portion (nip portion) of a pair of fixing rollers in the fixing device 28 , and the toner image is fixed to the recording paper P, thereby forming a fixed image.

[0310] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copy machines, printers, etc. Examples of the recording medium include OHP sheets, etc., in addition to the recording paper P.

[0311] In order to further improve the smoothness of the image surface after fixing, the surface of the recording paper P is preferably smooth, and for example, coated paper obtained by coating the surface of ordinary paper with a resin or the like, art paper for printing, etc. are preferably used.

[0312] The recording paper P on which the color image has been fixed is discharged toward the discharge portion, and a series of color image forming operations are completed.

[0313] <Processing box>

[0314] The processing box of this embodiment is a processing box that is equipped with a developing device and is detachable from the image forming device. The developing device accommodates the electrostatic charge image developer of this embodiment and develops the electrostatic charge image formed on the surface of the image holding body into a colorant image with the electrostatic charge image developer.

[0315] The process cartridge of this embodiment is not limited to the above-described structure, but may be a structure including a developing device and, if necessary, at least one of other devices selected from an image holder, a charging device, an electrostatic charge image forming device, and a transfer device.

[0316] An example of the process cartridge of the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and the description of the others is omitted.

[0317] Figure 3 It is a schematic structural diagram showing a process cartridge according to this embodiment.

[0318] Figure 3 The processing box 200 shown is composed of, for example, a frame 117 having a mounting rail 116 and an opening 118 for exposure, by which a photosensitive body 107 (an example of an image retaining body), a charging roller 108 (an example of a charging device) provided around the photosensitive body 107, a developing device 111 and a photosensitive body cleaning device 113 (an example of a cleaning device) are integrally combined and retained to form a box.

[0319] Figure 3 In the figure, 109 denotes an exposure device (an example of an electrostatic charge image forming device), 112 denotes a transfer device, 115 denotes a fixing device, and 300 denotes recording paper (an example of a recording medium).

[0320] [Example]

[0321] Hereinafter, the embodiments of the present invention will be described in detail by way of examples, but the embodiments of the present invention are not limited to these examples. In the following description, "parts" and "%" are based on mass unless otherwise specified.

[0322] [Production of ferrite particles]

[0323] <Production of ferrite particles (1)>

[0324] 1318 parts of Fe 2 O 3 , 2587 parts of Mn(OH), and 296 parts of Mg(OH) were mixed and pre-baked at 900°C for 4 hours. The pre-baked product, 6.6 parts of polyvinyl alcohol, 0.5 parts of polycarboxylic acid as a dispersant, and zirconia beads with a medium diameter of 1 mm were added to water, crushed and mixed with a sand mill to obtain a dispersion. The volume average particle size of the particles in the dispersion was 1.5 μm.

[0325] The dispersion was used as a raw material, and granulation and drying were performed using a spray dryer to obtain a granular material with a volume average particle size of 33 μm. Next, a formal calcination was performed at a temperature of 1350°C for 4 hours in an oxygen-nitrogen mixed atmosphere with an oxygen partial pressure of 1.2% using an electric furnace, and then heated at a temperature of 850°C for 3 hours in the air to obtain calcined particles. The calcined particles were crushed and classified to obtain ferrite particles (1) with a number average particle size of 30 μm. The obtained ferrite particles (1) have internal voids, and the internal void ratio is 5%.

[0326] <Production of ferrite particles (6)>

[0327] Ferrite particles (6) having a number average particle size of 30 μm were obtained in the same manner as ferrite particles (1) except that the oxygen partial pressure and temperature during the main calcination were set at 1.4% and 1250° C. The obtained ferrite particles (6) had internal voids and an internal void ratio of 8%.

[0328] <Production of ferrite particles (16)>

[0329] Ferrite particles (16) having a number average particle size of 30 μm were obtained in the same manner as ferrite particles (1) except that the oxygen partial pressure and temperature during the main calcination were set to 1.6% and 1150° C., respectively. The obtained ferrite particles (16) had internal voids and an internal void ratio of 12%.

[0330] <Production of ferrite particles (101)>

[0331] Ferrite particles (101) having a number average particle size of 31 μm were obtained in the same manner as ferrite particles (1), except that the oxygen partial pressure and temperature during the main calcination were set to 1.3% and 1325° C., respectively, and the heating temperature in the atmosphere was set to 900° C. The obtained ferrite particles (101) had internal voids and an internal void ratio of 6%.

[0332] <Production of ferrite particles (102)>

[0333] Ferrite particles (102) having a number average particle size of 31 μm were obtained in the same manner as ferrite particles (101) except that the oxygen partial pressure and temperature during the main calcination were set to 0.5% and 1500° C. The obtained ferrite particles (102) had internal voids and an internal void ratio of 2%.

[0334] <Production of ferrite particles (103)>

[0335] Ferrite particles (103) having a number average particle size of 31 μm were obtained in the same manner as ferrite particles (101) except that the oxygen partial pressure and temperature during the main calcination were set to 1.5% and 1200° C. The obtained ferrite particles (103) had internal voids and an internal void ratio of 10%.

[0336] <Production of ferrite particles (104)>

[0337] Ferrite particles (104) having a number average particle size of 31 μm were obtained in the same manner as ferrite particles (101) except that the oxygen partial pressure and temperature during the main calcination were set to 0.5% and 1550° C. The obtained ferrite particles (104) had internal voids and an internal void ratio of 1%.

[0338] <Production of ferrite particles (105)>

[0339] Ferrite particles (105) having a number average particle size of 31 μm were obtained in the same manner as ferrite particles (101) except that the oxygen partial pressure and temperature during the main calcination were set to 1.6% and 1150° C. The obtained ferrite particles (105) had internal voids and an internal void ratio of 12%.

[0340] [Preparation of coating agent]

[0341] The following coating agents (1) to (5) and (7) to (14) were prepared as a resin liquid that served as both a resin liquid for disposing a specific resin composition and a resin liquid for forming a resin coating layer.

[0342] <Preparation of coating agent (1)>

[0343] Resin (1): Cyclohexyl methacrylate polymer (weight average molecular weight: 350,000) 15.4 parts

[0344] Resin (2): 2-(dimethylamino)ethyl methacrylate polymer (weight average molecular weight: 300,000) 0.39 parts

[0345] Specific inorganic particles (1): 9.0 parts of silicon dioxide (number average particle size: 12 nm, fumed silica particles surface-treated with hexamethyldisilazane)

[0346] Conductive particles (1): 2.24 parts of carbon black (number average particle size: 30 nm, manufactured by Cabot Corporation, product name: Vulcan XC72)

[0347] Nitrogen-containing resin particles: 3.0 parts of melamine resin particles (Epostar S (manufactured by Nippon Shokubai Co., Ltd.)

[0348] Solvent: 150 parts of toluene

[0349] The above materials and glass beads (1 mm in diameter, the same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (1).

[0350] <Preparation of coating agents (2) to (5)>

[0351] Coating agents (2) to (5) were obtained in the same manner as in the coating agent (1) except that the addition amount of the specific inorganic particles (1) was changed to 14.4 parts, 5.4 parts, 18 parts, and 3.6 parts, respectively.

[0352] <Preparation of coating agents (7) to (10)>

[0353] Coating agents (7) to (10) were obtained in the same manner as in the coating agent (1) except that the following specific inorganic particles (7) to (10) were added in the following amounts, respectively, instead of the specific inorganic particles (1).

[0354] Specific inorganic particles (7): 9.0 parts of silicon dioxide (number average particle size: 5 nm, fumed silica particles surface-treated with hexamethyldisilazane)

[0355] Specific inorganic particles (8): 9.0 parts of silicon dioxide (number average particle size: 90 nm, fumed silica particles surface-treated with hexamethyldisilazane)

[0356] Specific inorganic particles (9): 9.0 parts of alumina (number average particle size: 13 nm, alumina particles surface-treated with octylsilane)

[0357] Specific inorganic particles (10): calcium carbonate (number average particle size: 40 nm, calcium carbonate particles not subjected to hydrophobic treatment) 9.0 parts

[0358] <Preparation of coating agents (11) to (12)>

[0359] Coating agents (11) to (12) were obtained in the same manner as the coating agent (1) and the coating agent (7) except that the following conductive particles (11) were added in the following amounts instead of the conductive particles (1).

[0360] Conductive particles (11): carbon black (number average particle size: 55 nm, manufactured by Mitsubishi Chemical Corporation, product name: #3030B) 2.24 parts

[0361] <Preparation of coating agent (13)>

[0362] A coating agent (13) was obtained in the same manner as the coating agent (1) except that the resin (2) was not added.

[0363] <Preparation of coating agent (14)>

[0364] A coating agent (14) was obtained in the same manner as in the coating agent (1) except that the specific inorganic particles (1) were not added.

[0365] The following resin liquids were prepared as the resin liquid for disposing the specific resin composition and the resin liquid for forming the resin coating layer.

[0366] [Preparation of resin liquid]

[0367] <Preparation of resin solution (1-1)>

[0368] Resin: Cyclohexyl methacrylate polymer (weight average molecular weight: 150,000) 5.2 parts

[0369] Specific inorganic particles (1): 0.25 parts of silicon dioxide (number average particle size: 12 nm, fumed silica particles surface-treated with hexamethyldisilazane)

[0370] Solvent: 100 parts toluene

[0371] The above materials and glass beads (1 mm in diameter, the same amount as toluene) were put into a sand mill and stirred at a rotation speed of 500 rpm for 30 minutes to obtain a resin liquid (1-1).

[0372] <Preparation of resin solutions (1-2) to (1-15) and resin solutions (2-1) to (2-12)>

[0373] Resin liquids (1-2) to (1-15) and resin liquids (2-1) to (2-12) were obtained in the same manner as resin liquid (1-1) except that the amount of resin added, the type and amount of specific inorganic particles added, and the amount of solvent added were changed as shown in Tables 1 to 2.

[0374] [Table 1]

[0375]

[0376] [Table 2]

[0377]

[0378] [Preparation of carrier]

[0379] <Preparation of carrier (1)>

[0380] 1000 parts of ferrite particles (1) and 180 parts of coating agent (1) were placed in a vacuum degassing kneader and stirred at 75°C and -20 kPa (gauge pressure) for 2 hours. The temperature was then raised to 85°C and toluene was distilled off at a vacuum degree of -90 kPa (gauge pressure) to form a carrier in which the ferrite particles were coated with a resin. Subsequently, fine powder and coarse powder were removed using an elbo w-jet classifier to obtain a carrier (1). The average thickness of the resin coating layer in the carrier (1) was 1.10 μm.

[0381] The cross section of the obtained carrier (1) was confirmed, and it was confirmed that a specific resin composition containing silica and resin was arranged in the internal voids of the ferrite particles (1). The results of the area ratio (SP / SR) and the area ratio (SC / SP) in the specific resin composition obtained by the above method are shown in Table 3.

[0382] <Preparation of carriers (2) to (5) and (7) to (14)>

[0383] Carriers (2) to (5) and (7) to (14) were obtained in the same manner as carrier (1), except that coating agents (2) to (5) and (7) to (14) were used, respectively, instead of coating agent (1). The average thickness of the resin coating layer in carriers (2) to (5) and (7) to (14) was 1.26 μm, 0.99 μm, 1.36 μm, 0.93 μm, 1.10 μm, 1.10 μm, 1.00 μm, 1.05 μm, 1.1 μm, 1.1 μm, 1.09 μm, and 0.81 μm, respectively.

[0384] The cross sections of the obtained carriers (2) to (5) and (7) to (13) were confirmed, and the results showed that a specific resin composition containing silica and a resin was arranged in the internal voids of the ferrite particles (1). The results of the area ratio (SP / SR) and the area ratio (SC / SP) in the specific resin composition obtained by the above method are shown in Table 3.

[0385] On the other hand, when the cross section of the carrier (14) was checked, it was confirmed that only the resin was arranged in the internal voids of the ferrite particles (1).

[0386] <Preparation of carrier (6)>

[0387] A carrier (6) was obtained in the same manner as in the carrier (1) except that the ferrite particles (6) were used instead of the ferrite particles (1). The average thickness of the resin coating layer in the carrier (6) was 1.10 μm.

[0388] The cross section of the obtained carrier (6) was confirmed, and it was confirmed that a specific resin composition containing silica and resin was arranged in the internal voids of the ferrite particles (6). The results of the area ratio (SP / SR) and the area ratio (SC / SP) in the specific resin composition obtained by the above method are shown in Table 3.

[0389] <Preparation of carrier (15)>

[0390] 1000 parts of ferrite particles (1) and 180 parts of coating agent (1) were placed in a vacuum degassing kneader and stirred at 60°C and -20 kPa (gauge pressure) for 1 hour. The temperature was then raised to 70°C and toluene was distilled off at a vacuum degree of -75 kPa (gauge pressure) to form a carrier in which the ferrite particles were coated with a resin. Subsequently, fine powder and coarse powder were removed using an elbo w-jet classifier to obtain a carrier (15). The average thickness of the resin coating layer in the carrier (15) was 1.10 μm.

[0391] The cross section of the obtained carrier (15) was examined, and it was confirmed that neither silica nor the resin was arranged in the internal voids of the ferrite particles (1).

[0392] <Preparation of carrier (16)>

[0393] A carrier (16) was obtained in the same manner as in the carrier (1) except that the ferrite particles (16) were used instead of the ferrite particles (1). The average thickness of the resin coating layer in the carrier (16) was 1.10 μm.

[0394] The cross section of the obtained carrier (16) was confirmed, and it was confirmed that a specific resin composition containing silica and resin was arranged in the internal voids of the ferrite particles (16). The results of the area ratio (SP / SR) and the area ratio (SC / SP) in the specific resin composition obtained by the above method are shown in Table 3.

[0395] <Preparation of carrier (101)>

[0396] 3000 parts of ferrite particles (101) and 100 parts of resin liquid (1-1) are placed in a vacuum degassing kneader, heated to 50°C at normal pressure, and mixed and stirred for 30 minutes (first step). Then, 730 parts of resin liquid (2-1) are added, the temperature is raised to 70°C, and stirred at -80 kPa (gauge pressure) for 1 hour (second step). Then, the temperature is raised to 80°C and the pressure is reduced to -90 kPa (gauge pressure), and toluene is distilled off. Next, an elbow-jet classifier is used to remove fine powder and coarse powder to obtain a carrier (101). The average thickness of the resin coating layer in the carrier (101) is 1.02 μm.

[0397] The obtained carrier (101) was confirmed in cross section, and it was confirmed that a specific resin composition containing silica and resin was arranged in the internal voids of the ferrite particles (101), and the specific resin composition was connected to the resin coating layer. The results of determining the area ratio A in the resin coating layer ("A" in the table), the area ratio B in the specific resin composition ("B" in the table), and the value of the area ratio B / area ratio A ("B / A" in the table) by the above method are shown in Table 4.

[0398] <Preparation of carriers (102) to (120)>

[0399] Carriers (102) to (120) were obtained in the same manner as carrier (101), except that the type of ferrite particles used, the type of resin solution used in the first step, and the type of resin solution used in the second step were changed as shown in Table 4. "-" in the resin solution in the following table indicates that the step was omitted.

[0400] In addition, the average thickness of the resin coating layer in the carriers (102) to (120) is 0.97μm, 1.05μm, 0.95μm, 1.05μm, 1.02μm, 1.02μm, 1.02μm, 1.02μm, 1μm, 0.98μm, 0.95μm, 1.03μm, 1.1μm, 0.98μm, 1.1μm, 0.95μm, 0.93μm, 1.0μm, and 1.02μm, respectively.

[0401] The cross sections of the obtained carriers (102) to (115), (118), and (120) were confirmed, and the results showed that a specific resin composition containing silica and resin was arranged in the internal voids of the ferrite particles, and the specific resin composition was connected to the resin coating layer. On the other hand, the cross sections of the carriers (116) and (117) were confirmed, and the results showed that only the resin was arranged in the internal voids of the ferrite particles. In addition, the cross section of the carrier (119) was confirmed, and the results showed that neither the resin nor the inorganic particles were arranged in the internal voids of the ferrite particles.

[0402] For the obtained carrier, the area ratio A in the resin coating layer ("A" in the table), the area ratio B in the specific resin composition ("B" in the table), and the value of the area ratio B / area ratio A ("B / A" in the table) obtained by the above method are shown in Table 4.

[0403] [Production of developer]

[0404] Any one of the obtained carriers (1) to (16), (101) to (120) and the colorant obtained by the method described later are placed in a V-type mixer at a mixing ratio of carrier:colorant = 100:10 (mass ratio), and stirred for 20 minutes to obtain developers (1) to (16), (101) to (120), respectively.

[0405] [evaluate]

[0406] <Evaluation of density unevenness of solid images>

[0407] A modified image forming apparatus Apeos C4030 (manufactured by Fujifilm Business Innovation Co., Ltd.) of a development method in which an AC voltage is applied was prepared, and the obtained developer was placed in the developer. Under high temperature and high humidity (35°C, 75% RH), 50,000 test images (solid images) with a cyan image density of 100% were output on A3 size paper. For the 50,000th image (test image), 9 points of the image portion were measured using an image densitometer (X-Rite 938, manufactured by X-Rite Corporation), and the standard deviation σ of the obtained density E was calculated and evaluated according to the following evaluation criteria.

[0408] -Evaluation Criteria-

[0409] A: The standard deviation σ of the density E of the test image is less than 0.05.

[0410] B: The standard deviation σ of the density E of the test image is 0.05 or more and less than 0.07.

[0411] B-: The standard deviation σ of the density E of the test image is 0.07 or more and less than 0.10.

[0412] B--: The standard deviation σ of the density E of the test image is 0.10 or more and less than 0.13.

[0413] C: The standard deviation σ of the density E of the test image is 0.13 or more and less than 0.18.

[0414] D: The standard deviation σ of the density E of the test image is 0.18 or more.

[0415] <Evaluation of carrier adhesion>

[0416] A modified machine of the image forming device DocuPrintColor3540 (manufactured by Fujifilm Business Innovation Co., Ltd.) was prepared, and the obtained developer was placed in the developer. After continuously forming 100,000 cyan high-density images (solid images with an image density of 100%) on A3-sized paper at high temperature and high humidity (28°C, 85% RH), the device was forced to stop after forming an image with two 2cm×2cm patches. After that, an adhesive tape was pressed against the developing part on the photoreceptor, and the adhesive surface of the tape was observed through an optical microscope. Thus, the adhesive tape was pressed against the developing part on the photoreceptor, and the adhesive surface of the tape was observed through an optical microscope. 2 The number of carriers (including crushed fine powder) attached to the adhesive surface of the photosensitive body was counted. This operation was performed on two developing parts on the photosensitive body, and the average value was calculated and evaluated. In addition, the evaluation criteria were as follows, and G1 to G3 were acceptable levels. The results are shown in Table 4 ("Attachment" in the table).

[0417] -Evaluation Criteria-

[0418] G1: 0-1

[0419] G1.5: 2 to 3

[0420] G2: 4-5

[0421] G2.5: 6-7

[0422] G3: 8-9

[0423] G4: 10-11

[0424] G5: 12 or more

[0425] <Evaluation of image density>

[0426] For the first image and the 100,000th image of the 100,000 solid images formed in the evaluation of the above-mentioned carrier attachment, the 9 points of the image portion were measured respectively using an image densitometer (X-Rite938, manufactured by X-Rite Corporation), and the average value of the obtained concentration E was calculated for each image. The average value of the concentration E in the first image was set as E1, and the average value of the concentration E in the 100,000th image was set as E2. The change rate of the concentration was calculated by the following formula, and the evaluation was performed according to the following evaluation criteria. The results are shown in Table 4 ("Concentration" in the table).

[0427] Formula: Reduction rate = |(E1-E2)| / E1

[0428] -Evaluation Criteria-

[0429] G1: Change rate is less than 0.05

[0430] G2: The rate of change is 0.05 or more and less than 0.1

[0431] G3: The rate of change is greater than 0.1 and less than 0.2

[0432] [Table 3]

[0433]

[0434] [Table 4]

[0435]

[0436] The above results show that, in the present example, the density unevenness of the image formed by the development method in which an AC voltage is applied under a high temperature and high humidity environment is suppressed as compared with the comparative example.

[0437] In addition, the abbreviations in the table are as follows.

[0438] ·CHMA: Cyclohexyl methacrylate polymer

[0439] DMAEMA: 2-(Dimethylamino)ethyl methacrylate polymer

[0440] Area ratio (SP / SR): ratio of the total area SP of the specific inorganic particles in the cross section of the specific resin composition to the total area SR of the resin.

[0441] Area ratio (SC / SP): ratio of the total area SC of the conductive particles in the cross section of the specific resin composition to the total area SP of the specific inorganic particles

[0442] [Preparation of toner]

[0443] The toner used in the preparation of the above-mentioned developer is obtained by the following method.

[0444] <Preparation of resin particle dispersion (1)>

[0445]

[0446] The above materials were placed in a flask, and the temperature was raised to 200°C over 1 hour. After confirming that the reaction system was uniformly stirred, 1.2 parts of dibutyltin oxide were added. The generated water was distilled off, and the temperature was raised to 240°C over 6 hours. Stirring was continued at 240°C for 4 hours to obtain a polyester resin (acid value 9.4 mgKOH / g, weight average molecular weight 13,000, glass transition temperature 62°C). The polyester resin was transferred to an emulsifier disperser (Cavitron CD1010, Eurotec) at a rate of 100 g per minute in a molten state. In addition, a 0.37% concentration of dilute ammonia water obtained by diluting the reagent ammonia water with ion exchange water was placed in a tank, and while being heated to 120°C with a heat exchanger, it was transferred to the emulsifier disperser at a rate of 0.1 liter per minute while transferring the polyester resin. The emulsifier disperser was set at a rotor rotation speed of 60 Hz and a pressure of 5 kg / cm 2 The reaction mixture was operated under the conditions of , and a resin particle dispersion (1) having a volume average particle size of 160 nm and a solid content of 30% was obtained.

[0447] <Preparation of Resin Particle Dispersion (2)>

[0448] · Sebacic acid (Tokyo Chemical Industry Co., Ltd.) 81 parts

[0449] · Hexanediol (Fujifilm Wako Pure Chemical Industries, Ltd.) 47 parts

[0450] The above materials were placed in a flask, and the temperature was raised to 160°C over 1 hour. After confirming that the reaction system was uniformly stirred, 0.03 parts of dibutyltin oxide was added. The temperature was raised to 200°C over 6 hours while the generated water was distilled off, and stirring was continued at 200°C for 4 hours. Next, the reaction solution was cooled, solid-liquid separation was performed, and the solid matter was dried at a temperature of 40°C / under reduced pressure to obtain a polyester resin (C1) (melting point 64°C, weight average molecular weight 15,000).

[0451] ·Polyester resin (C1) 50 parts

[0452] · Anionic surfactant (Neogen SC, Daiichi Kogyo Seiyaku Co., Ltd.) 2 parts

[0453] 200 parts of ion exchange water

[0454] The above materials were heated to 120°C, fully dispersed with a homogenizer (ULTRA-TURRAXT50, IKA Corporation), and then dispersed with a pressure ejection homogenizer. When the volume average particle size reached 180 nm, a resin particle dispersion (2) with a solid content of 20% was obtained.

[0455] <Preparation of Colorant Particle Dispersion (1)>

[0456] · Blue-green pigment (Pigment Blue 15:3, Dainichi Seika Industries, Ltd.) 10 parts

[0457] · Anionic surfactant (Neogen SC, Daiichi Kogyo Seiyaku Co., Ltd.) 2 parts

[0458] 80 parts of ion exchange water

[0459] The above materials were mixed and dispersed for 1 hour using a high-pressure impact disperser (ultimizer HJP30006, Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (1) having a volume average particle size of 180 nm and a solid content of 20%.

[0460] <Preparation of Release Agent Particle Dispersion (1)>

[0461] Paraffin wax (HNP-9, Nippon Seira Co., Ltd.) 50 parts

[0462] · Anionic surfactant (Neogen SC, Daiichi Kogyo Seiyaku Co., Ltd.) 2 parts

[0463] 200 parts of ion exchange water

[0464] The above materials were heated to 120°C, fully dispersed with a homogenizer (ULTRA-TURRAXT50, IKA), and then dispersed with a pressure ejection homogenizer. When the volume average particle size reached 200 nm, a release agent particle dispersion (1) with a solid content of 20% was obtained.

[0465] <Production of toner particles>

[0466]

[0467] The above materials were placed in a round stainless steel flask, and after being fully mixed and dispersed using a homogenizer (ULTRA-TURRAXT50, IKA), the mixture was heated to 48°C in a heating oil bath while being stirred in the flask. After the reaction system was kept at 48°C for 60 minutes, 70 parts of the resin particle dispersion (1) were slowly added. Next, the pH was adjusted to 8.0 using a 0.5 mol / L aqueous sodium hydroxide solution, the flask was sealed, the seal of the stirring shaft was magnetically sealed, and the mixture was heated to 90°C and maintained for 30 minutes while being continuously stirred. Next, the mixture was cooled at a temperature drop rate of 5°C / min, solid-liquid separation was performed, and the mixture was fully washed with ion exchange water. Next, solid-liquid separation was performed, the mixture was dispersed in ion exchange water at 30°C, stirred at a rotation speed of 300 rpm for 15 minutes, and washed. This washing operation was further repeated 6 times. When the pH of the filtrate reached 7.54 and the conductivity reached 6.5 μS / cm, solid-liquid separation was performed and vacuum drying was continued for 24 hours to obtain toner particles (1) having a volume average particle size of 5.7 μm.

[0468] <External addition of toner particles>

[0469] 100 parts of the above-mentioned toner particles (1) and 0.7 parts of hydrophobic silica (RY50 manufactured by Nippon Aerosil Co., Ltd.) were mixed with a Henschel mixer to obtain a toner.

[0470] (Note) (((1)))

[0472] A carrier for electrostatic charge image development, comprising:

[0473] Magnetic particles having internal voids; and

[0474] A resin composition is disposed in at least a portion of the internal voids and contains inorganic particles including at least one selected from the group consisting of silica, alumina, and calcium carbonate, and a resin. (((2)))

[0476] The electrostatic charge image developing carrier according to (((1))), wherein

[0477] The internal porosity of the magnetic particles is 2% or more and 10% or less. (((3)))

[0479] The electrostatic charge image developing carrier according to (((1))) or (((2))), wherein:

[0480] In a cross section of the resin composition, a ratio of a total area of ​​the inorganic particles to a total area of ​​the resin is 0.02 or more and 0.10 or less. (((4)))

[0482] The electrostatic charge image developing carrier according to any one of (((1))) to (((3))), wherein

[0483] The resin composition does not contain conductive particles; or contains the conductive particles, and in a cross section of the resin composition, a ratio of a total area of ​​the conductive particles to a total area of ​​the inorganic particles is 0.005 or less. (((5)))

[0485] The electrostatic charge image developing carrier according to any one of (((1))) to (((4))), wherein

[0486] The inorganic particles have a number average particle size of 5 nm or more and 90 nm or less. (((6)))

[0488] The electrostatic charge image developing carrier according to any one of (((1))) to (((5))), wherein

[0489] The resin includes a resin having a nitrogen atom. (((7)))

[0491] The electrostatic charge image developing carrier according to (((6))), wherein

[0492] The resin also includes a resin having no nitrogen atom. (((8)))

[0494] The electrostatic charge image developing carrier according to (((1))), wherein

[0495] A resin coating layer is provided, the resin coating layer coating the magnetic particles and containing a resin and inorganic particles. (((9)))

[0497] The electrostatic charge image developing carrier according to (((8))), wherein

[0498] When the ratio of the total area of ​​the inorganic particles contained in the resin coating layer to the overall area of ​​the resin coating layer in the cross-section of the resin coating layer is set as area ratio A, and the ratio of the total area of ​​the inorganic particles contained in the resin composition to the overall area of ​​the resin composition in the cross-section of the resin composition is set as area ratio B, the area ratio A is greater than 10% and less than 50%, and the area ratio A>area ratio B. (((10)))

[0500] The electrostatic charge image developing carrier according to (((9))), wherein

[0501] The area ratio B is greater than or equal to 0.05 times the area ratio A and less than or equal to 0.3 times. (((11)))

[0503] An electrostatic charge image developer, comprising:

[0504] Toner for developing electrostatic charge images; and

[0505] The electrostatic charge image developing carrier according to any one of (((1))) to (((10))). (((12)))

[0507] A processing box, wherein

[0508] A developing device is provided, wherein the developing device contains the electrostatic charge image developer described in (((11))), and develops the electrostatic charge image formed on the surface of the image holding member into a toner image by the electrostatic charge image developer,

[0509] The process cartridge is attachable to and detachable from the image forming apparatus. (((13)))

[0511] An image forming device, comprising:

[0512] Like holding body;

[0513] a charging device, the charging device charging the surface of the image holding body;

[0514] an electrostatic charge image forming device for forming an electrostatic charge image on the surface of the charged image holding body;

[0515] a developing device containing the electrostatic charge image developer described in (((11))) and developing the electrostatic charge image formed on the surface of the image holding member into a toner image by means of the electrostatic charge image developer;

[0516] a transfer device that transfers the toner image formed on the surface of the image holding body to the surface of a recording medium; and

[0517] A fixing device fixes the toner image transferred onto the surface of the recording medium. (((14)))

[0519] An image forming method, comprising:

[0520] A charging process for charging the surface of the image holder;

[0521] an electrostatic charge image forming step of forming an electrostatic charge image on the surface of the charged image holding body;

[0522] a developing step of developing the electrostatic charge image formed on the surface of the image holding member into a toner image using the electrostatic charge image developer described in (((11)));

[0523] a transfer step of transferring the toner image formed on the surface of the image holding member to the surface of a recording medium; and

[0524] The fixing step fixes the toner image transferred to the surface of the recording medium.

[0525] According to (((1))), there is provided an electrostatic image developing carrier which suppresses density unevenness of an image formed by a development method applying an alternating voltage under a high temperature and high humidity environment, compared with a case where no inorganic particles are contained in the internal voids of magnetic particles.

[0526] According to (((2))), there is provided a carrier for electrostatic image development which suppresses density unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where the internal porosity of magnetic particles is less than 2% or exceeds 10%.

[0527] According to (((3))), there is provided a carrier for electrostatic charge image development, which suppresses the concentration unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where the ratio of the total area of ​​inorganic particles to the total area of ​​resin in a cross section of the resin composition is less than 0.02 or exceeds 0.10.

[0528] According to (((4))), there is provided a carrier for electrostatic charge image development, which suppresses the concentration unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where the ratio of the total area of ​​the conductive particles to the total area of ​​the inorganic particles in the cross section of the resin composition exceeds 0.005.

[0529] According to (((5))), there is provided a carrier for electrostatic image development, which suppresses density unevenness of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with a case where the number average particle size of inorganic particles is less than 5 nm or exceeds 90 nm.

[0530] According to (((6))), there is provided an electrostatic image developing carrier which suppresses density unevenness of an image formed by a development method in which an AC voltage is applied under a high temperature and high humidity environment, compared with a case where the resin does not contain a resin having a nitrogen atom.

[0531] According to (((7))), there is provided an electrostatic image developing carrier which suppresses the poor environment of image density compared with the case where the resin is composed of a resin having nitrogen atoms.

[0532] According to (((8))), there is provided a carrier for electrostatic image development, which, compared with a case where the resin coating layer or the resin composition arranged in the internal voids does not contain inorganic particles, suppresses the adhesion of the carrier for electrostatic image development to the image retaining body when an image with high image density is continuously formed for a long time under high temperature and high humidity.

[0533] According to (((9))), there is provided a carrier for electrostatic charge image development, which suppresses the adhesion of the carrier for electrostatic charge image development to the image retaining body when an image with high image density is continuously formed for a long time under high temperature and high humidity, compared with the case where the area ratio A is less than 10% or exceeds 50%, or the area ratio A ≤ area ratio B.

[0534] According to (((10))), there is provided a carrier for electrostatic charge image development, which suppresses the adhesion of the carrier for electrostatic charge image development to the image retaining body when an image with high image density is continuously formed for a long time under high temperature and high humidity, compared with a case where the area ratio B is less than 0.05 times or exceeds 0.3 times the area ratio A.

[0535] According to (((11))), (((12))), (((13))), or (((14))), an electrostatic charge image developer, a processing box, an image forming device, or an image forming method is provided, which suppresses the uneven concentration of an image formed by a development method applying an AC voltage under a high temperature and high humidity environment, compared with the case where an electrostatic charge image developing carrier is used in which the internal gaps of the magnetic particles do not contain inorganic particles.

Claims

1. A carrier for electrostatic charge image development, characterized in that: have: Magnetic particles having internal voids; and A resin composition is disposed in at least a portion of the internal voids and contains inorganic particles including at least one selected from the group consisting of silica, alumina, and calcium carbonate, and a resin.

2. The electrostatic charge image developing carrier according to claim 1, wherein: The internal porosity of the magnetic particles is 2% or more and 10% or less.

3. The electrostatic charge image developing carrier according to claim 1 or 2, wherein: In a cross section of the resin composition, a ratio of a total area of ​​the inorganic particles to a total area of ​​the resin is 0.02 or more and 0.10 or less.

4. The electrostatic charge image developing carrier according to any one of claims 1 to 3, wherein The resin composition does not contain conductive particles; or contains the conductive particles, and in a cross section of the resin composition, a ratio of a total area of ​​the conductive particles to a total area of ​​the inorganic particles is 0.005 or less.

5. The electrostatic charge image developing carrier according to any one of claims 1 to 4, wherein The inorganic particles have a number average particle size of 5 nm or more and 90 nm or less.

6. The electrostatic charge image developing carrier according to any one of claims 1 to 5, wherein The resin includes a resin having a nitrogen atom.

7. The electrostatic charge image developing carrier according to claim 6, wherein: The resin also includes a resin having no nitrogen atom.

8. The electrostatic charge image developing carrier according to claim 1, wherein: A resin coating layer is provided, the resin coating layer coating the magnetic particles and containing a resin and inorganic particles.

9. The electrostatic charge image developing carrier according to claim 8, wherein: When the ratio of the total area of ​​the inorganic particles contained in the resin coating layer to the overall area of ​​the resin coating layer in the cross-section of the resin coating layer is set as area ratio A, and the ratio of the total area of ​​the inorganic particles contained in the resin composition to the overall area of ​​the resin composition in the cross-section of the resin composition is set as area ratio B, the area ratio A is greater than 10% and less than 50%, and the area ratio A>area ratio B.

10. The electrostatic charge image developing carrier according to claim 9, wherein: The area ratio B is greater than or equal to 0.05 times the area ratio A and less than or equal to 0.3 times.

11. An electrostatic charge image developer, characterized in that: Include: Toner for developing electrostatic charge images; and The electrostatic charge image developing carrier according to any one of claims 1 to 10.

12. A processing box, characterized in that: A developing device is provided, wherein the developing device contains the electrostatic charge image developer according to claim 11, and develops the electrostatic charge image formed on the surface of the image holding member into a toner image by the electrostatic charge image developer, The process cartridge is attachable to and detachable from the image forming apparatus.

13. An image forming device, characterized in that: have: Like holding body; a charging device, the charging device charging the surface of the image holding body; an electrostatic charge image forming device for forming an electrostatic charge image on the surface of the charged image holding body; a developing device containing the electrostatic charge image developer according to claim 11, and developing the electrostatic charge image formed on the surface of the image holding member into a toner image by the electrostatic charge image developer; a transfer device for transferring the toner image formed on the surface of the image holding body to the surface of a recording medium; as well as A fixing device fixes the toner image transferred onto the surface of the recording medium.

14. An image forming method, characterized in that: have: A charging process for charging the surface of the image holder; an electrostatic charge image forming step of forming an electrostatic charge image on the surface of the charged image holding body; a developing step of developing the electrostatic charge image formed on the surface of the image holding member into a toner image using the electrostatic charge image developer according to claim 11; a transfer step of transferring the toner image formed on the surface of the image holding member to the surface of a recording medium; as well as The fixing step fixes the toner image transferred onto the surface of the recording medium.

Citation Information

Patent Citations

  • Electrostatic latent image developing carrier and developer for electrostatic latent image development

    JP2007058124A

  • Carrier core material, carrier for developing electrophotography using the same, and developer for electrophotography

    JP2019061188A

  • Electrostatic image developing carrier, electrostatic image developer, process cartridge, image forming device, and image forming method

    JP2021051216A